Ultraviolet curable adhesive composition and method for producing laminate

By using a specific proportion of maleimide derivatives, ultraviolet polymerizable compounds, photopolymerization initiators and amine compounds in the ultraviolet curing adhesive composition, the problems of poor stress relief and poor curing properties when curing in the presence of oxygen are solved, and the bonding effect of high impact resistance and low exudity is achieved.

CN119654386APending Publication Date: 2025-03-18SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380060839.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-01
Filing Date
2023-11-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When the conventional ultraviolet curing adhesive composition cures in the presence of oxygen, the high crosslinking density leads to poor stress relief, and poor outermost surface curability leads to the generation of exudates, affecting adhesion.

Method used

A specific ratio of maleimide derivatives, ultraviolet polymerizable compounds, photopolymerization initiators and amine compounds is used to improve surface curability through hydrogen capture reactions, and a monomer capable of becoming a hydrogen donor is used to increase the reaction rate.

Benefits of technology

An ultraviolet curing adhesive composition with excellent printing properties, no cohesive damage to cured substances, and excellent impact resistance is achieved, ensuring adhesion and low exudity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to an ultraviolet-curable adhesive composition containing a maleimide derivative, an ultraviolet-polymerizable compound, a photopolymerization initiator, and an amine compound, and in a case where the maleimide derivative contains a maleimide derivative that does not have a structure that is hydrogen-bonded to a hetero atom, the photopolymerization initiator is a photopolymerization initiator that does not have a structure that is hydrogen-bonded to the hetero atom. The maleimide derivative does not contain a maleimide derivative having a structure that is hydrogen-bonded to a heteroatom, or the content of the maleimide derivative having a structure that is hydrogen-bonded to a heteroatom in the maleimide derivative is less than 50 mass%. When the maleimide derivative contains only a maleimide derivative having a structure that is hydrogen-bonded to a heteroatom, the content of the maleimide derivative having a structure that is hydrogen-bonded to a heteroatom is 9.8 parts by mass or less with respect to 100 parts by mass of the ultraviolet-polymerizable compound, and the content of the maleimide derivative having a structure that is hydrogen-bonded to a heteroatom is 9.8 parts by mass or less with respect to 100 parts by mass of the ultraviolet-polymerizable compound. The ultraviolet polymerizable compound contains 20% by mass or more of a monomer capable of becoming a hydrogen donor, and the photopolymerization initiator contains at least one type selected from the group consisting of hydrogen abstracting type photopolymerization initiators and polymer type photopolymerization initiators. The content of an amine compound that does not have a structure that is hydrogen-bonded to a heteroatom in the amine compound is 50% by mass or more, and the content of the amine compound is 0.1-10 parts by mass (inclusive) per 100 parts by mass of the total of the maleimide derivative and the ultraviolet-polymerizable compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an ultraviolet curable adhesive composition and a method for producing a laminated body using the ultraviolet curable adhesive composition. Background Art

[0002] Adhesives are used in the lamination of electronic components inside electronic devices such as smart phones and PCs. In the usual method of lamination using adhesives, first, an adhesive sheet with spacers respectively arranged on both sides of the adhesive is made, and then the adhesive sheet is cut into a desired shape. Then, a spacer is peeled off from the cut adhesive sheet, and one side of the exposed adhesive is laminated with the first adherend, and then another spacer is peeled off, and the other side of the exposed adhesive is laminated with the second adherend. In the case of this method, since a part of the adhesive sheet is discarded after cutting, waste is generated. In addition, bubbles sometimes enter the lamination surface.

[0003] In view of this, a method of printing an adhesive composition into a desired shape without preparing an adhesive sheet and then laminating it to an adherend has been studied. This method can suppress the generation of waste and prevent air bubbles from entering the laminating surface.

[0004] For example, Patent Document 1 discloses an invention for providing a radiation-curable adhesive composition that can be finely patterned and exhibits high adhesion to various adherends such as metals and plastics. Patent Document 1 describes a radiation-curable adhesive composition containing 10 to 70% by weight of an ethylenically unsaturated monomer not containing an aromatic ring, 1 to 10% by weight of a photopolymerization initiator, and 10 to 55% by weight of a crosslinking agent.

[0005] In addition, Patent Document 2 discloses an invention for providing a photocurable adhesive composition that provides a laminate having an adhesive strength equivalent to that in the absence of oxygen even when light irradiation is performed in the presence of oxygen. Patent Document 2 describes a photocurable adhesive composition comprising (A) a (meth)acrylate oligomer, (B) a monofunctional (meth)acrylic monomer, (C) a 2- to 4-functional (meth)acrylic monomer, (D) a photoreaction initiator, (E) a tackifier having a softening point of 70 to 150° C., and (F) a liquid plasticizer.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-216742

[0009] Patent Document 2: International Publication No. 2016 / 163152 Summary of the invention

[0010] Problems to be solved by the invention

[0011] As mentioned above, according to the method for laminating with adherend after adhesive composition is printed into desired shape without making adhesive sheet, the generation of waste can be suppressed, and bubbles can also be prevented from entering the laminating surface.On the other hand, as the method for adhesive composition being cured, in order to avoid the heating of adherend, preferably ultraviolet curing, but in the case of wanting to obtain the high curable solidified material by ultraviolet curing in the presence of oxygen, because the cross-linking density becomes high and the stress relaxation property deteriorates, as a result, the impact resistance of solidified material deteriorates sometimes.In addition, if adhesive composition is not covered by spacer and exposed in the presence of oxygen when curing, the outermost surface is uncured, and adhesiveness can't be fully obtained sometimes.In addition, due to the poor curability of the outermost surface and exudate, due to the existence of this exudate, when using adhesive composition to laminating adherend, sometimes slide along the shear direction.

[0012] The object of the present invention is to provide an ultraviolet curing adhesive composition having excellent printability, a cured product that is not prone to cohesive failure, and excellent impact resistance, and an ultraviolet curing adhesive composition having excellent adhesion and low exudation. In addition, the object of the present invention is to provide a method for producing a laminated body using the ultraviolet curing adhesive composition.

[0013] Means for solving problems

[0014] The present disclosure 1 relates to an ultraviolet curable adhesive composition, which contains a maleimide derivative, an ultraviolet polymerizable compound, a photopolymerization initiator and an amine compound, wherein, when the maleimide derivative contains a maleimide derivative having no structure of hydrogen bonding to a heteroatom, the maleimide derivative does not contain a maleimide derivative having a structure of hydrogen bonding to a heteroatom, or the content of the maleimide derivative having a structure of hydrogen bonding to a heteroatom in the maleimide derivative is less than 50% by mass, and when the maleimide derivative contains only a maleimide derivative having a structure of hydrogen bonding to a heteroatom, the content of the maleimide derivative having a structure of hydrogen bonding to a heteroatom is less than 50% by mass relative to the ultraviolet polymerizable compound. The invention relates to a method for preparing an ultraviolet-polymerizable compound, wherein the content of the maleimide derivative having a structure in which hydrogen is bonded to a heteroatom is 9.8 parts by mass or less, the ultraviolet-polymerizable compound comprises 20% by mass or more of a monomer that can serve as a hydrogen donor, the photopolymerization initiator comprises at least one selected from a hydrogen abstraction type photopolymerization initiator and a polymer type photopolymerization initiator, and regarding the amine compound, the content of the amine compound that does not have a structure in which hydrogen is bonded to a heteroatom in the amine compound is 50% by mass or more, and the content of the amine compound is 0.1 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the total of the maleimide derivative and the ultraviolet-polymerizable compound.

[0015] The present disclosure 2 relates to the ultraviolet curable adhesive composition of the present disclosure 1, wherein the content of the maleimide derivative is 0.1 parts by mass or more and 20 parts by mass or less based on 100 parts by mass of the ultraviolet polymerizable compound.

[0016] Disclosure 3 relates to the ultraviolet curable adhesive composition of Disclosure 1 or 2, wherein the monomer capable of serving as a hydrogen donor is a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group and an amide bond.

[0017] The present disclosure 4 relates to the ultraviolet curable adhesive composition of the present disclosure 1, 2 or 3, wherein the ultraviolet curable adhesive composition is applied on a substrate, and the total irradiation dose is 900 mJ / cm in an atmospheric environment without sealing the upper surface of the coating layer. 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The reaction rate of the cured product with a thickness of 100 μm was 85% or more.

[0018] The present disclosure 5 relates to an ultraviolet curable adhesive composition, which contains a maleimide derivative, an ultraviolet polymerizable compound and a photopolymerization initiator, wherein the content of the maleimide derivative is 8 parts by mass or more relative to 100 parts by mass of the ultraviolet polymerizable compound, and the ultraviolet curable adhesive composition is applied on a substrate, and the total irradiation amount is 900 mJ / cm in an atmospheric environment without sealing the upper surface of the coating layer. 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The reaction rate of the cured product with a thickness of 100 μm was 88% or more.

[0019] The present disclosure 6 relates to the ultraviolet curable adhesive composition of the present disclosure 5, further comprising an amine compound.

[0020] Disclosure 7 relates to the UV-curable adhesive composition of Disclosure 1, 2, 3, 4, 5 or 6, wherein the UV-polymerizable compound contains 50% by mass or more of a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group and an amide bond.

[0021] Disclosure 8 relates to the ultraviolet curable adhesive composition of Disclosure 1, 2, 3, 4, 5, 6 or 7, wherein the ultraviolet polymerizable compound includes at least one selected from the group consisting of a (meth)acrylic monomer and a vinyl monomer.

[0022] The present disclosure 9 relates to the ultraviolet curable adhesive composition of the present disclosure 8, wherein the ultraviolet polymerizable compound contains a polyfunctional (meth)acrylic monomer.

[0023] The present disclosure 10 relates to the ultraviolet curable adhesive composition of the present disclosure 9, wherein the above-mentioned ultraviolet polymerizable compound contains a polyfunctional (meth)acrylic monomer, and the content of the above-mentioned polyfunctional (meth)acrylic monomer is 25 parts by mass or less relative to 100 parts by mass of the total of the above-mentioned maleimide derivative and the above-mentioned ultraviolet polymerizable compound other than the above-mentioned polyfunctional (meth)acrylic monomer.

[0024] The present disclosure 11 relates to the ultraviolet curable adhesive composition of the present disclosure 10, wherein the content of the above-mentioned polyfunctional (meth)acrylic monomer is 20 parts by mass or less relative to 100 parts by mass of the total of the above-mentioned maleimide derivative and the above-mentioned ultraviolet polymerizable compound excluding the above-mentioned polyfunctional (meth)acrylic monomer.

[0025] Disclosure 12 relates to the ultraviolet curable adhesive composition of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or 11, wherein the content of the photopolymerization initiator is 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the total of the maleimide derivative and the ultraviolet polymerizable compound.

[0026] Disclosure 13 relates to the ultraviolet curable adhesive composition of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, further comprising a thermoplastic resin.

[0027] Disclosure 14 relates to the ultraviolet curable adhesive composition of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, further comprising a tackifier.

[0028] The present disclosure 15 relates to the ultraviolet curable adhesive composition of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, which has a viscosity of 10 mPa·s or more and 75000 mPa·s or less at 25°C.

[0029] Disclosure 16 relates to the ultraviolet curable adhesive composition of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, wherein the ultraviolet curable adhesive composition is applied to a substrate so that the total irradiation amount becomes 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The glass transition temperature of the cured product having a thickness of 100 μm obtained by irradiating the cured product with light is not less than −60° C. and not more than 20° C.

[0030] The present disclosure 17 relates to a method for manufacturing a laminate, which comprises: a step of forming an adhesive layer by applying the ultraviolet-curable adhesive composition of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16 on a first adherend and exposing the composition to light; and a step of attaching a second adherend to the adhesive layer, wherein the method for applying the ultraviolet-curable adhesive composition is inkjet printing, screen printing, spraying, spin coating, gravure offset printing or reverse offset printing, and the ultraviolet-curable adhesive composition is locally applied to the first adherend.

[0031] Hereinafter, the present invention will be described in detail.

[0032] Hereinafter, the ultraviolet curable adhesive composition of the present disclosure 1 is also referred to as the "ultraviolet curable adhesive composition of the present disclosure 1", and the ultraviolet curable adhesive composition of the present disclosure 5 is also referred to as the "ultraviolet curable adhesive composition of the present disclosure 2". In addition, matters common to the ultraviolet curable adhesive composition of the present disclosure 1 and the ultraviolet curable adhesive composition of the present disclosure 2 are described as "the ultraviolet curable adhesive composition of the present disclosure".

[0033] The present inventors have studied the use of a specific maleimide derivative, a specific ultraviolet polymerizable compound, a specific photopolymerization initiator, and a specific amine compound in combination in a specific content ratio in an ultraviolet curing adhesive composition. As a result, it was found that an ultraviolet curing adhesive composition with excellent printability, in which the cured product is not prone to cohesive failure and has excellent impact resistance can be obtained, thereby completing the present invention 1. In addition, the present inventors have studied: a maleimide derivative, an ultraviolet polymerizable compound, and a photopolymerization initiator are used in combination in an ultraviolet curing adhesive composition, and the reaction rate of the cured product of the ultraviolet curing adhesive composition cured under specific conditions is made to be above a specific value on the basis of making the content of the photopolymerization initiator within a specific range. As a result, it was found that an ultraviolet curing adhesive composition with excellent adhesion and low exudation can be obtained, thereby completing the present invention 2.

[0034] The ultraviolet curable adhesive composition of the present invention contains a maleimide derivative.

[0035] The reaction system of the maleimide derivative is basically carried out through a hydrogen abstraction (Type II) reaction. The photoradical polymerization based on the hydrogen abstraction reaction is not easily hindered by oxygen, so the surface curability can be improved. In addition, in the photoradical polymerization based on the hydrogen abstraction reaction, a branched polymer is obtained instead of a linear polymer as in the cleavage (Type I) reaction, and the cohesive force is also increased. Therefore, the ultraviolet curable adhesive composition of the present invention can obtain a cured product that is not prone to bleeding accompanied by reduced surface curability and cohesive failure accompanied by reduced surface curability and cohesive force by combining the maleimide derivative and the ultraviolet polymerizable compound described later.

[0036] It should be noted that, in the present specification, the above-mentioned "maleimide derivative" refers to a compound having a maleimide group. In addition, the above-mentioned maleimide derivative has ultraviolet polymerizability, but is not regarded as an ultraviolet polymerizable compound described later.

[0037] In the ultraviolet curable adhesive composition of the present invention 1, when the maleimide derivative includes a maleimide derivative having no structure of hydrogen bonding to a heteroatom, the maleimide derivative does not include a maleimide derivative having a structure of hydrogen bonding to a heteroatom, or the content of the maleimide derivative having a structure of hydrogen bonding to a heteroatom in the maleimide derivative is less than 50% by mass, and when the maleimide derivative includes only a maleimide derivative having a structure of hydrogen bonding to a heteroatom, the content of the maleimide derivative having a structure of hydrogen bonding to a heteroatom is 9.8 parts by mass or less relative to 100 parts by mass of the ultraviolet polymerizable compound. Thus, the cured product of the ultraviolet curable adhesive composition of the present invention has excellent impact resistance. It is particularly preferred that the maleimide derivative includes only a maleimide derivative having no structure of hydrogen bonding to a heteroatom.

[0038] Examples of the structure in which hydrogen is bonded to a hetero atom include a hydroxyl group, a carboxyl group, a primary amino group, and a secondary amino group.

[0039] Examples of the monofunctional maleimide in the maleimide derivatives not having a structure in which hydrogen bonds are formed to heteroatoms include N-cyclohexylmaleimide, N-laurylmaleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-benzylmaleimide, N-phenylmethylmaleimide, N-octadecenylmaleimide, and N-dodecenylmaleimide. Among them, at least one selected from N-cyclohexylmaleimide and N-laurylmaleimide is preferred.

[0040] In addition, examples of the polyfunctional maleimide in the maleimide derivative having no structure in which hydrogen is bonded to a hetero atom include N,N'-methylenebismaleimide, N,N'-trimethylenebismaleimide, N,N'-dodecamethylenebismaleimide, N,N'-(4,4'-diphenylmethane)bismaleimide, 1,4-dimaleimide cyclohexane, isophorone biscarbamate bis(N-ethylmaleimide), N,N'-p-phenylenebismaleimide, N,N'-m-phenylenebismaleimide, N,N'-m-tolylenebismaleimide, Amine, N,N'-4,4'-biphenylene bismaleimide, N,N'-4,4'-(3,3'-dimethylbiphenylene) bismaleimide, N,N'-4,4'-(3,3'-dimethyldiphenylmethane) bismaleimide, N,N'-4,4'-(3,3'-diethyldiphenylmethane) bismaleimide, N,N'-4,4'-diphenylpropane bismaleimide, N,N'-4,4'-diphenyl ether bismaleimide, N,N'-3,3'-diphenyl sulfone bismaleimide, N,N'-4,4'-diphenyl sulfone bismaleimide, etc.

[0041] From the viewpoint of improving the reaction rate, the monofunctional maleimide and these polyfunctional maleimides may be used in combination as the maleimide derivative having no structure hydrogen-bonded to a heteroatom. However, the combined use of a large amount of polyfunctional maleimide is not preferred because the gel fraction increases.

[0042] Examples of the maleimide derivative having a structure in which hydrogen is bonded to a hetero atom include N-(4-carboxycyclohexylmethyl)maleimide, 4-hydroxyphenylmaleimide, and N-(4-anilinophenyl)maleimide.

[0043] Examples of the monofunctional maleimide in the maleimide derivative in the ultraviolet curable adhesive composition of the second embodiment include N-cyclohexylmaleimide, N-laurylmaleimide, 4-hydroxyphenylmaleimide, N-(4-carboxycyclohexylmethyl)maleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-(2-chlorophenyl)maleimide, N-methylmaleimide, Maleimide, N-ethylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-benzylmaleimide, N-phenylmethylmaleimide, N-(2,4,6-tribromophenyl)maleimide, N-[3-(triethoxysilyl)propyl]maleimide, N-octadecenylmaleimide, N-dodecenylmaleimide, N-(2-methoxyphenyl)maleimide, N-(2,4,6-trichlorophenyl)maleimide, N-(1-hydroxyphenyl)maleimide, etc. Among them, from the viewpoint of improving the reaction rate, it is desirable to select a maleimide derivative having a structure that does not hydrogen bond to a hetero atom. In addition, from the viewpoint of improving the adhesive force, a maleimide derivative having a structure that hydrogen bonds to a hetero atom can be used. Specifically, the monofunctional maleimide is preferably at least one selected from the group consisting of N-cyclohexylmaleimide, 4-hydroxyphenylmaleimide, and N-(4-carboxycyclohexylmethyl)maleimide.

[0044] In addition, examples of the polyfunctional maleimide in the maleimide derivatives include N,N'-methylenebismaleimide, N,N'-trimethylenebismaleimide, N,N'-dodecamethylenebismaleimide, N,N'-(4,4'-diphenylmethane)bismaleimide, 1,4-dimaleimide cyclohexane, isophorone biscarbamate bis(N-ethylmaleimide), N,N'-p-phenylenebismaleimide, N,N'-m-phenylenebismaleimide, N,N'-m-toluenebismaleimide, N,N'-4,4'-diphenylmethanebismaleimide, and N,N'-m-toluenebismaleimide. 4'-Biphenylene bismaleimide, N,N'-4,4'-(3,3'-dimethylbiphenylene) bismaleimide, N,N'-4,4'-(3,3'-dimethyldiphenylmethane) bismaleimide, N,N'-4,4'-(3,3'-diethyldiphenylmethane) bismaleimide, N,N'-4,4'-diphenylpropane bismaleimide, N,N'-4,4'-diphenyl ether bismaleimide, N,N'-3,3'-diphenyl sulfone bismaleimide, N,N'-4,4'-diphenyl sulfone bismaleimide, etc.

[0045] From the viewpoint of improving the reaction rate, the above-mentioned monofunctional maleimide and these polyfunctional maleimides may be used in combination as the maleimide derivative. However, since the gel fraction increases, it is not preferred to use a large amount of polyfunctional maleimide in combination.

[0046] In the ultraviolet curable adhesive composition of the present invention 1, the preferred lower limit of the content of the maleimide derivative is 0.1 parts by mass, and the preferred upper limit is 20 parts by mass, relative to 100 parts by mass of the ultraviolet polymerizable compound described later. By setting the content of the maleimide derivative in the ultraviolet curable adhesive composition of the present invention 1 to be within the above range, the curability of the obtained ultraviolet curable adhesive composition becomes more excellent. The more preferred lower limit of the content of the maleimide derivative in the ultraviolet curable adhesive composition of the present invention 1 is 0.5 parts by mass, and the more preferred upper limit is 10 parts by mass.

[0047] In the ultraviolet curable adhesive composition of the second invention, the lower limit of the content of the maleimide derivative is 8 parts by mass relative to 100 parts by mass of the ultraviolet polymerizable compound described later. By making the content of the maleimide derivative in the ultraviolet curable adhesive composition of the second invention 8 parts by mass or more, the surface curability of the obtained ultraviolet curable adhesive composition is excellent. The preferred lower limit of the content of the maleimide derivative in the ultraviolet curable adhesive composition of the second invention is 10 parts by mass, the more preferred lower limit is 12 parts by mass, and the further preferred lower limit is 14 parts by mass.

[0048] In addition, from the viewpoint of reaction rate, the upper limit of the content of the maleimide derivative in the ultraviolet curable adhesive composition of the present invention 2 is preferably 70 parts by mass, and the more preferred upper limit is 30 parts by mass, relative to 100 parts by mass of the ultraviolet polymerizable compound described later.

[0049] The ultraviolet curable adhesive composition of the present invention contains an ultraviolet polymerizable compound.

[0050] As described above, the ultraviolet curable adhesive composition of the present invention contains the ultraviolet polymerizable compound and the maleimide derivative in combination, thereby obtaining a cured product that is less likely to bleed out due to reduced surface curability and less likely to cause cohesive failure due to reduced curability and cohesive strength.

[0051] In the ultraviolet curable adhesive composition of the first aspect of the present invention, the ultraviolet polymerizable compound contains a monomer that can serve as a hydrogen donor. In the ultraviolet curable adhesive composition of the second aspect of the present invention, the ultraviolet polymerizable compound preferably contains a monomer that can serve as a hydrogen donor.

[0052] It should be noted that, in the present specification, the above-mentioned “monomer capable of serving as a hydrogen donor” refers to a monomer having hydrogen that can be donated to a hydrogen abstraction reaction.

[0053] The monomer capable of being a hydrogen donor is preferably a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group and an amide bond. By making the monomer capable of being a hydrogen donor a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group and an amide bond, it is possible to more easily react hydrogen donation with hydrogen abstraction. Among them, the monomer capable of being a hydrogen donor is more preferably a monomer having at least one structure selected from an ether bond, a phenoxy group and an amide bond.

[0054] In the ultraviolet curable adhesive composition of the present invention 1, the lower limit of the content of the monomer capable of being a hydrogen donor in the ultraviolet polymerizable compound is 20% by mass. By making the content of the monomer capable of being a hydrogen donor in the ultraviolet polymerizable compound 20% by mass or more, the curability of the ultraviolet curable adhesive composition of the present invention becomes excellent. The preferred lower limit of the content of the monomer capable of being a hydrogen donor in the ultraviolet polymerizable compound is 35% by mass.

[0055] From the viewpoint of impact resistance, the upper limit of the content of the monomer capable of serving as a hydrogen donor in the ultraviolet polymerizable compound is preferably 90% by mass, and the more preferably 70% by mass.

[0056] In particular, in the ultraviolet curable adhesive composition of the present invention, the ultraviolet polymerizable compound preferably contains 50% by mass or more of a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond. By making the ultraviolet polymerizable compound contain 50% by mass or more of a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond, the surface curability of the obtained ultraviolet curable adhesive composition and the impact resistance of the cured product become more excellent. The ultraviolet polymerizable compound more preferably contains 70 parts by mass or more of a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond in 100 parts by mass of the (meth) acrylic monomer.

[0057] Furthermore, the (meth)acrylic monomer may include only a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond.

[0058] The ultraviolet polymerizable compound preferably includes at least one selected from (meth)acrylic monomers and vinyl monomers. By making the ultraviolet polymerizable compound include at least one selected from (meth)acrylic monomers and vinyl monomers, the curability of the obtained ultraviolet curable adhesive composition becomes more excellent.

[0059] In the present specification, the “(meth)acrylic acid” refers to acrylic acid or methacrylic acid, the “(meth)acrylic monomer” refers to a monomer having a (meth)acryloyl group, and the “(meth)acryloyl group” refers to an acryloyl group or a methacryloyl group.

[0060] From the viewpoint of adhesion to various substrates, etc., the (meth)acrylic monomer preferably includes a monofunctional (meth)acrylic monomer.

[0061] In the present specification, the “monofunctional (meth)acrylic monomer” refers to a monomer having one (meth)acryloyl group in one molecule.

[0062] Examples of the monofunctional (meth)acrylic monomer include monofunctional (meth)acrylate compounds and monofunctional (meth)acrylamide compounds.

[0063] Examples of the monofunctional (meth)acrylate compound include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-heptyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and propyl (meth)acrylate. 2-Hydroxybutyl (meth)acrylate, 4-Hydroxybutyl (meth)acrylate, Cyclohexyl (meth)acrylate, Isobornyl (meth)acrylate, Dicyclopentenyl (meth)acrylate, Benzyl (meth)acrylate, 2-Methoxyethyl (meth)acrylate, 2-Ethoxyethyl (meth)acrylate, 2-Butoxyethyl (meth)acrylate, 2-Phenoxyethyl (meth)acrylate, Methoxyethylene glycol (meth)acrylate, Methoxypolyethylene glycol (meth)acrylate, Phenoxydiethylene glycol (meth)acrylate, Phenoxypolyethylene glycol (meth)acrylate, Tetrahydrofurfuryl (meth)acrylate, Tetrahydrofurfuryl alcohol acrylate polymerル)、ethyl carbitol (meth)acrylate、2,2,2-trifluoroethyl (meth)acrylate、2,2,3,3-tetrafluoropropyl (meth)acrylate、1H,1H,5H-octafluoropentyl (meth)acrylate、imido (meth)acrylate、dimethylaminoethyl (meth)acrylate、diethylaminoethyl (meth)acrylate、2-(meth)acryloyloxyethyl succinate、2-(meth)acryloyloxyethyl hexahydrophthalate、2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate、2-(meth)acryloyloxyethyl phosphate、(meth)acrylate (3-ethyloxetan-3-yl)methyl ester、(meth)acrylate 2-(((butylamino)carbonyl) oxy) ethyl (meth)acrylate, (3-propyloxetane-3-yl)methyl (meth)acrylate, (3-butyloxetane-3-yl)methyl (meth)acrylate, (3-ethyloxetane-3-yl)ethyl (meth)acrylate, (3-ethyloxetane-3-yl)propyl (meth)acrylate, (3-ethyloxetane-3-yl)butyl (meth)acrylate, (3-ethyloxetane-3-yl)pentyl (meth)acrylate, (3-ethyloxetane-3-yl)hexyl (meth)acrylate, γ-butyrolactone (meth)acrylate, (2,2-dimethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methyl ester, (meth)acrylate (2-methyl-2-isobutyl-1,3-dioxolan-4-yl) methyl ester, (meth)acrylate (2-cyclohexyl-1,3-dioxolan-4-yl) methyl ester, cyclic trimethylolpropane formal acrylate, etc.

[0064] It should be noted that, in the present specification, the above-mentioned “(meth)acrylate” means acrylate or methacrylate.

[0065] Examples of the monofunctional (meth)acrylamide compound include N,N-dimethyl (meth)acrylamide, N-(meth)acryloylmorpholine, N-hydroxyethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, and N,N-dimethylaminopropyl (meth)acrylamide.

[0066] The ultraviolet polymerizable compound may contain a polyfunctional (meth)acrylic monomer as the (meth)acrylic monomer. The polyfunctional (meth)acrylic monomer has a function as a cross-linking component.

[0067] In addition, in this specification, the said "polyfunctional (meth)acrylic-based monomer" means a monomer which has two or more (meth)acryloyl groups in one molecule.

[0068] Examples of the polyfunctional (meth)acrylic monomer include polyfunctional urethane (meth)acrylates, polyfunctional (meth)acrylate compounds, and polyfunctional epoxy (meth)acrylates.

[0069] In addition, in this specification, the said "epoxy (meth)acrylate" means the compound obtained by making all epoxy groups in an epoxy compound react with (meth)acrylic acid.

[0070] The polyfunctional urethane (meth)acrylate can be obtained, for example, by reacting a (meth)acrylic acid derivative having a hydroxyl group with an isocyanate compound in the presence of a catalytic amount of a tin-based compound.

[0071] Examples of the isocyanate compound used as a raw material for the polyfunctional urethane (meth)acrylate include isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4′-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, dimethylbiphenyl diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)phosphorothioate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.

[0072] Furthermore, as the isocyanate compound serving as a raw material of the polyfunctional urethane (meth)acrylate, a chain-extended isocyanate compound obtained by a reaction between a polyol and an excess of an isocyanate compound may be used.

[0073] Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.

[0074] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of diols, and mono(meth)acrylates or di(meth)acrylates of triols.

[0075] Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate.

[0076] Examples of the diol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol.

[0077] Examples of the triol include trimethylolethane, trimethylolpropane, and glycerin.

[0078] Examples of the polyfunctional (meth)acrylate compound include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate. (Meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide added bisphenol A di(meth)acrylate, propylene oxide added bisphenol A di(meth)acrylate, ethylene oxide added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate Ester, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide added trimethylolpropane tri(meth)acrylate, propylene oxide added trimethylolpropane tri(meth)acrylate, caprolactone modified trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate Acrylate, ethylene oxide added isocyanuric acid tri(meth)acrylate, glycerol tri(meth)acrylate, propylene oxide added glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tri(meth)acryloyloxyethyl phosphate, di(trimethylolpropane) tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol monohydroxy penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, caprolactone modified dipentaerythritol hexa(meth)acrylate, etc.

[0079] Examples of the polyfunctional epoxy (meth)acrylate include bisphenol A epoxy (meth)acrylate, bisphenol F epoxy (meth)acrylate, bisphenol E epoxy (meth)acrylate, and caprolactone-modified products thereof.

[0080] In the ultraviolet curable adhesive composition of the present invention 1, the preferred upper limit of the content of the above-mentioned multifunctional (meth) acrylic monomer is 25 parts by mass relative to the total of 100 parts by mass of the above-mentioned maleimide derivative and the above-mentioned ultraviolet polymerizable compound other than the above-mentioned multifunctional (meth) acrylic monomer. By making the content of the above-mentioned multifunctional (meth) acrylic monomer in the ultraviolet curable adhesive composition of the present invention 1 25 parts by mass or less, the printability of the obtained ultraviolet curable adhesive composition and the impact resistance of the cured product are further improved. The more preferred upper limit of the content of the above-mentioned multifunctional (meth) acrylic monomer in the ultraviolet curable adhesive composition of the present invention 1 is 20 parts by mass.

[0081] In addition, from the viewpoint of impact resistance and adhesive strength, in the ultraviolet curable adhesive composition of the present invention 1, the preferred lower limit of the content of the above-mentioned multifunctional (meth) acrylic monomer is 5 parts by mass relative to 100 parts by mass of the total of the above-mentioned maleimide derivative and the above-mentioned ultraviolet polymerizable compound other than the above-mentioned multifunctional (meth) acrylic monomer.

[0082] In the ultraviolet curable adhesive composition of the second invention, the preferred lower limit of the content of the above-mentioned multifunctional (meth) acrylic monomer is 1 part by mass, and the preferred upper limit is 30 parts by mass, relative to the total of 100 parts by mass of the above-mentioned maleimide derivative and the above-mentioned ultraviolet polymerizable compound other than the above-mentioned multifunctional (meth) acrylic monomer. By making the content of the above-mentioned multifunctional (meth) acrylic monomer in the ultraviolet curable adhesive composition of the second invention within this range, the adhesion of the cured product formed by the obtained ultraviolet curable adhesive composition becomes more excellent. The more preferred lower limit of the content of the above-mentioned multifunctional (meth) acrylic monomer in the ultraviolet curable adhesive composition of the second invention is 3 parts by mass, the more preferred upper limit is 25 parts by mass, the further preferred upper limit is 20 parts by mass, and the particularly preferred upper limit is 15 parts by mass.

[0083] As the vinyl monomer, an amide compound having a vinyl group is preferred, and a cyclic amide compound having a vinyl group is more preferred.

[0084] The cyclic amide compound having a vinyl group preferably has a lactam structure, and is more preferably a compound represented by the following formula (1).

[0085] [Chemical formula 1]

[0086]

[0087] In formula (1), n ​​represents an integer of 2 to 6.

[0088] Examples of the compound represented by the formula (1) include N-vinyl-2-pyrrolidone and N-vinyl-ε-caprolactam. Among them, N-vinyl-ε-caprolactam is preferred.

[0089] Among the amide compounds having a vinyl group, examples of compounds other than the cyclic amide compounds having a vinyl group include N-vinylacetamide and the like.

[0090] In the ultraviolet curable adhesive composition of the present invention 1, when the ultraviolet polymerizable compound includes the (meth) acrylic monomer and the vinyl monomer, the preferred lower limit of the content of the vinyl monomer is 20 parts by mass, and the preferred upper limit is 80 parts by mass relative to 100 parts by mass of the (meth) acrylic monomer. By making the content of the vinyl monomer in the ultraviolet curable adhesive composition of the present invention 1 more than 20 parts by mass, the curability of the obtained ultraviolet curable adhesive composition becomes more excellent. By making the content of the vinyl monomer in the ultraviolet curable adhesive composition of the present invention 1 less than 80 parts by mass, the properties other than the curability of the obtained ultraviolet curable adhesive composition can also be excellent. The more preferred lower limit of the content of the vinyl monomer in the ultraviolet curable adhesive composition of the present invention 1 is 40 parts by mass, and the more preferred upper limit is 60 parts by mass.

[0091] In addition, in the ultraviolet curable adhesive composition of the present invention 2, when the ultraviolet polymerizable compound includes the (meth) acrylic monomer and the vinyl monomer, the preferred lower limit of the content of the vinyl monomer is 8 parts by mass, and the preferred upper limit is 80 parts by mass relative to 100 parts by mass of the (meth) acrylic monomer. By making the content of the vinyl monomer in the ultraviolet curable adhesive composition of the present invention 2 more than 8 parts by mass, the curability of the obtained ultraviolet curable adhesive composition becomes more excellent. By making the content of the vinyl monomer in the ultraviolet curable adhesive composition of the present invention 2 less than 80 parts by mass, the properties other than the curability of the obtained ultraviolet curable adhesive composition can also be excellent. The more preferred lower limit of the content of the vinyl monomer in the ultraviolet curable adhesive composition of the present invention 2 is 15 parts by mass, and the more preferred upper limit is 60 parts by mass.

[0092] The ultraviolet curable adhesive composition of the present invention contains a photopolymerization initiator.

[0093] In the ultraviolet curable adhesive composition of the present invention 1, the photopolymerization initiator comprises at least one selected from a hydrogen abstraction type photopolymerization initiator and a polymer type photopolymerization initiator. By using such a photopolymerization initiator in combination with an amine compound described later, the ultraviolet curable adhesive composition obtained can obtain a cured product that is less likely to bleed out due to reduced surface curability and cohesive failure due to reduced surface curability and cohesive force.

[0094] In addition, in the ultraviolet curable adhesive composition of the present invention 2, the photopolymerization initiator preferably includes a hydrogen abstraction type photopolymerization initiator. By using the hydrogen abstraction type photopolymerization initiator as the photopolymerization initiator in combination with the amine compound described later, the ultraviolet curable adhesive composition obtained can obtain a cured product that is less likely to cause bleeding accompanied by reduced surface curability and cohesive failure accompanied by reduced surface curability and cohesive force.

[0095] As the hydrogen abstraction type photopolymerization initiator, a benzophenone-based photopolymerization initiator is preferred. Examples of the benzophenone-based photopolymerization initiator include benzophenone, 4-chlorobenzophenone, 4,4′-dimethylbenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, methyl o-benzoylbenzoate, 3,3′-dimethyl-4-methoxybenzophenone, 4-phenylbenzophenone, 4-benzoyl-4′-methyl-diphenyl sulfide, 4-morpholinobenzophenone, 4,4′-diphenoxybenzophenone, 4-hydroxybenzophenone, 2-carboxybenzophenone, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methyl-propionyl)-benzyl)-phenyl)-2-methyl-propane-1-one, 1-(4-(4-benzoylphenylthio)phenyl)-2-tosyl-2-methyl-1-propanone, and 3-coumarinone.

[0096] Examples of commercially available products of the hydrogen abstraction type photopolymerization initiator include Esacure TZT and Omnirad 4MBZ (both manufactured by IGM Resins Co., Ltd.).

[0097] Examples of the polymeric photopolymerization initiator include polymers of ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate, polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butyrylphenyl)piperazine)propionate, and polyethylene glycol bis(benzophenone-2-carboxylate).

[0098] Examples of commercially available products of the polymer-type photopolymerization initiator include Omnipol TP, Omnipol 910, and Omnipol 2702 (all manufactured by IGM Resins Co., Ltd.).

[0099] In the ultraviolet curable adhesive composition of the second aspect of the present invention, a cleavage-type photopolymerization initiator may be used as the photopolymerization initiator.

[0100] Examples of the cleavage-type photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0101] In the ultraviolet curable adhesive composition of the present invention 1, the preferred lower limit of the content of the above-mentioned photopolymerization initiator is 0.5 parts by mass, and the preferred upper limit is 15 parts by mass, relative to the total of 100 parts by mass of the above-mentioned maleimide derivative and the above-mentioned ultraviolet polymerizable compound. By making the content of the above-mentioned photopolymerization initiator in the ultraviolet curable adhesive composition of the present invention 1 within this range, the storage stability, curability and adhesion of the obtained ultraviolet curable adhesive composition become more excellent. The more preferred lower limit of the content of the above-mentioned photopolymerization initiator in the ultraviolet curable adhesive composition of the present invention 1 is 1 part by mass, the more preferred upper limit is 10 parts by mass, the further preferred lower limit is 3 parts by mass, and the further preferred upper limit is 9 parts by mass.

[0102] In the ultraviolet curable adhesive composition of the second invention, the preferred lower limit of the content of the photopolymerization initiator is 1 part by mass, and the preferred upper limit is 10 parts by mass, relative to 100 parts by mass of the total of the maleimide derivative and the ultraviolet polymerizable compound. By making the content of the photopolymerization initiator in the ultraviolet curable adhesive composition of the second invention within this range, the storage stability, curability and adhesion of the obtained ultraviolet curable adhesive composition become more excellent. The more preferred lower limit of the content of the photopolymerization initiator in the ultraviolet curable adhesive composition of the second invention is 3 parts by mass, and the more preferred upper limit is 9 parts by mass.

[0103] The ultraviolet curable adhesive composition of the present invention 1 contains an amine compound.

[0104] Furthermore, the ultraviolet curable adhesive composition of the present invention 2 preferably further contains an amine compound.

[0105] As described above, by using the amine compound and the hydrogen abstraction type photopolymerization initiator in combination, the obtained ultraviolet curable adhesive composition can obtain a cured product that is less likely to cause bleeding due to reduced surface curability and cohesive failure due to reduced curability and cohesive strength.

[0106] In the ultraviolet curable adhesive composition of the present invention 1, regarding the above-mentioned amine compound, the content of the amine compound having a structure that does not hydrogen bond to a hetero atom in the amine compound is 50% by mass or more. By using an amine compound having a content of 50% by mass or more of the above-mentioned amine compound having a structure that does not hydrogen bond to a hetero atom, the obtained ultraviolet curable adhesive composition can obtain a cured product that is less likely to have oozing accompanied by reduced surface curability and cohesive failure accompanied by reduced surface curability and cohesive force. In the ultraviolet curable adhesive composition of the present invention 1, regarding the above-mentioned amine compound, the content of the amine compound having a structure that does not hydrogen bond to a hetero atom is preferably 75% by mass or more, and most preferably 100% by mass.

[0107] Examples of the amine compound having a structure not having a hydrogen bond to a hetero atom include (bis-N,N-(4-dimethylaminobenzoyl)oxyethylene-1-yl)-methylamine, bis(2-morpholinoethyl) ether, 1-methyl 10-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidinyl)butane-1,2,3,4-tetracarboxylate, and bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate.

[0108] Examples of commercially available products of the amine compound not having a structure in which hydrogen is bonded to a hetero atom include Esacure A198 (manufactured by IGM Resins), U-cat 660 (manufactured by San-Apro), Eversorb 93 (manufactured by Everlight Chemical), ADK STAB LA-52, and ADK STAB LA-72 (both manufactured by ADEKA).

[0109] In the ultraviolet curable adhesive composition of the second embodiment of the present invention, examples of the amine compound include (bis-N,N-(4-dimethylaminobenzoyl)oxyethylene-1-yl)-methylamine, bis(2-morpholinoethyl)ether, 1-methyl 10-(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, and bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate.

[0110] In the ultraviolet curable adhesive composition of the present invention 1, the lower limit of the content of the above-mentioned amine compound is 0.1 parts by mass and the upper limit is 10 parts by mass relative to the total of 100 parts by mass of the above-mentioned maleimide derivative and the above-mentioned ultraviolet polymerizable compound. By making the content of the above-mentioned amine compound in the ultraviolet curable adhesive composition of the present invention 1 more than 0.1 parts by mass, the curability of the obtained ultraviolet curable adhesive composition becomes excellent. By making the content of the above-mentioned amine compound in the ultraviolet curable adhesive composition of the present invention 1 less than 10 parts by mass, the cured product of the obtained ultraviolet curable adhesive composition is not prone to cohesive failure. The preferred lower limit of the content of the above-mentioned amine compound in the ultraviolet curable adhesive composition of the present invention 1 is 1.5 parts by mass, and the more preferred lower limit is 2.5 parts by mass. The preferred upper limit is 7 parts by mass, and the more preferred upper limit is 5 parts by mass.

[0111] In the ultraviolet curable adhesive composition of the present invention 2, the preferred lower limit of the content of the above-mentioned amine compound in the total of 100 parts by mass of the above-mentioned maleimide derivative and the above-mentioned ultraviolet polymerizable compound is 1.5 parts by mass, and the preferred upper limit is 8 parts by mass. By making the content of the above-mentioned amine compound in the ultraviolet curable adhesive composition of the present invention 2 more than 1.5 parts by mass, the surface curability of the obtained ultraviolet curable adhesive composition becomes more excellent. By making the content of the above-mentioned amine compound in the ultraviolet curable adhesive composition of the present invention 2 less than 8 parts by mass, the cured product of the obtained ultraviolet curable adhesive composition is not prone to cohesive failure. The more preferred lower limit of the content of the above-mentioned amine compound in the ultraviolet curable adhesive composition of the present invention 2 is 2.5 parts by mass, and the more preferred upper limit is 5 parts by mass.

[0112] The ultraviolet curable adhesive composition of the present invention may further contain a thermoplastic resin.

[0113] As the thermoplastic resin, a compound that does not contain a reactive double bond in the compound or substantially does not exhibit photoradical polymerization reactivity even if having a reactive double bond is preferred.

[0114] Examples of the thermoplastic resin include solvent-free acrylic polymers and polymers obtained by drying a polymer dissolved in a solvent.

[0115] Examples of the solvent-free acrylic polymer include polymers of at least one monomer selected from (meth)acrylic acid alkyl esters having an alkyl group with 1 to 20 carbon atoms, and copolymers of the monomer and other copolymerizable monomers.

[0116] Examples of commercially available products of the solvent-free acrylic polymers include ARUFON-UP1000 series, UH2000 series, and UC3000 series (all manufactured by Toagosei Co., Ltd.), KURARITY LA series, and KURARITY LK series (all manufactured by Kuraray Co., Ltd.).

[0117] The preferred lower limit of the content of the thermoplastic resin is 5 parts by mass, and the preferred upper limit is 100 parts by mass, relative to the total of 100 parts by mass of the maleimide derivative and the ultraviolet polymerizable compound. By making the content of the thermoplastic resin within this range, the viscosity of the obtained ultraviolet curable adhesive composition is improved, a thick coating film can be formed, the printability becomes more excellent, and the reduction of the adhesiveness at high temperature can be suppressed. The more preferred lower limit of the content of the thermoplastic resin is 20 parts by mass, and the more preferred upper limit is 60 parts by mass.

[0118] The ultraviolet curable adhesive composition may contain a substance that is reactive to a trigger such as heat or moisture by containing a thermosetting resin or a moisture curing resin.

[0119] Examples of the thermosetting resin include epoxy resins, phenol resins, urea resins, and melamine resins. Among them, epoxy resins are preferred.

[0120] Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, biphenyl epoxy resin, biphenyl novolac epoxy resin, biphenol epoxy resin, naphthalene epoxy resin, fluorene epoxy resin, phenol aralkyl epoxy resin, naphthol aralkyl epoxy resin, dicyclopentadiene epoxy resin, anthracene epoxy resin, epoxy resin having an adamantane skeleton, epoxy resin having a tricyclodecane skeleton, epoxy resin having a triazine core in the skeleton, and the like.

[0121] When the above-mentioned thermosetting resin is used, it is preferable that the ultraviolet curable adhesive composition contains a thermosetting agent.

[0122] Examples of the thermosetting agent include cyanate compounds (cyanate curing agents), phenol compounds (phenol thermosetting agents), amine compounds (amine thermosetting agents), thiol compounds (thiol thermosetting agents), imidazole compounds, phosphine compounds, acid anhydrides, active ester compounds, and dicyandiamide.

[0123] In addition, when epoxy resin is used as the above-mentioned thermosetting resin, the ultraviolet curable adhesive composition can contain a photocationic polymerization initiator. Thus, even after the active energy ray is irradiated in the first stage, curing is also easy to proceed slowly. As a result, the initial bonding force of the obtained ultraviolet curable adhesive composition becomes more excellent.

[0124] In addition, when the epoxy resin and the photocationic polymerization initiator are contained, the epoxy resin is not regarded as the ultraviolet-polymerizable compound.

[0125] The photocationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid by light irradiation, and may be an ionic photoacid generating type or a nonionic photoacid generating type.

[0126] Examples of the above-mentioned ionic photoacid generating type photocationic polymerization initiator include the following. That is, the cation part is an aromatic sulfonium, aromatic iodonium, aromatic diazo, aromatic ammonium, or (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe cation, and the anion part is BF4 - PF6 - 、SbF6 - , or (BX4) - The above X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups.

[0127] Examples of the aromatic sulfonium salt include bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(diphenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl-4-((phenylthio)phenyl)sulfonium hexafluorophosphate, diphenyl-4-((phenylthio)phenyl)sulfonium hexafluoroantimonate, diphenyl-4-((phenylthio)phenyl)sulfonium tetrakis(pentafluorophenyl)borate, and diphenyl-4-((phenylthio)phenyl)sulfonium tetrakis(pentafluorophenyl)borate. salt, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonyl)phenyl)sulfide bishexafluorophosphate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonyl)phenyl)sulfide bishexafluoroantimonate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonyl)phenyl)sulfide bistetrafluoroborate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonyl)phenyl)sulfide tetrakis(pentafluorophenyl)borate, and the like.

[0128] Examples of the aromatic diazonium salt include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, phenyldiazonium tetrafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate.

[0129] Examples of the aromatic ammonium salt include 1-benzyl-2-cyanopyridinium hexafluorophosphate, 1-benzyl-2-cyanopyridinium hexafluoroantimonate, 1-benzyl-2-cyanopyridinium tetrafluoroborate, 1-benzyl-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluorophosphate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluoroantimonate, 1-(naphthylmethyl)-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, and the like.

[0130] Examples of the (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salt include (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluorophosphate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluoroantimonate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrafluoroborate, and (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrakis(pentafluorophenyl)borate.

[0131] Examples of the nonionic photoacid-generating photocationic polymerization initiator include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, naphthoquinone diazide, and N-hydroxyimidesulfonic acid esters.

[0132] The above-mentioned photocationic polymerization initiators may be used alone or in combination of two or more.

[0133] The preferred lower limit of the amount of the photocationic polymerization initiator is 0.1 parts by mass, and the preferred upper limit is 10 parts by mass, relative to 100 parts by mass of the epoxy resin.

[0134] As the moisture-curable resin, for example, moisture-curable urethane resin, resin having a crosslinkable silyl group, etc. can be cited. Among them, moisture-curable urethane resin is preferred. Moisture-curable urethane resin has a urethane bond and an isocyanate group, and the isocyanate group in the molecule reacts with water to cure. It is preferred to have an isocyanate group at the end of the molecule.

[0135] The moisture-curable urethane resin may have a radical-reactive functional group. It should be noted that, when the moisture-curable urethane resin has a radical-reactive functional group, the moisture-curable urethane resin is not regarded as the ultraviolet-polymerizable compound.

[0136] The moisture-curable urethane resin can be obtained by reacting a polyol compound having two or more hydroxyl groups in one molecule with a polyisocyanate compound having two or more isocyanate groups in one molecule.

[0137] When the moisture-curable resin is used, it is preferred that the ultraviolet-curable adhesive composition contain a moisture-curing accelerator from the viewpoint of increasing the curing rate during moisture curing.

[0138] As said moisture curing accelerator, the compound which has a morpholine skeleton, the compound which has a piperidine skeleton, the compound which has a piperazine skeleton, etc. are mentioned, for example.

[0139] The ultraviolet curable adhesive composition of the present invention may further contain a tackifier.

[0140] Examples of the tackifier include rosin-based resins and terpene-based resins.

[0141] Examples of the rosin-based resin include rosin diol and the like.

[0142] The above-mentioned rosin diol is not particularly limited as long as it is a rosin-modified diol having a rosin skeleton and two hydroxyl groups in the molecule. A diol having a rosin component in the molecule is called a rosin polyol, and the skeleton other than the rosin component includes a polyether type such as polypropylene glycol (PPG), and a polyester type such as a condensed polyester polyol, a lactone polyester polyol, and a polycarbonate diol.

[0143] Examples of the rosin diol include rosin esters obtained by reacting rosin with a polyol, epoxy-modified rosin esters obtained by reacting rosin with an epoxy compound, and modified rosins having a hydroxyl group such as polyether having a rosin skeleton. These can be produced by conventionally known methods.

[0144] Examples of the rosin component include abietic acid and its derivatives, such as dehydroabietic acid, dihydroabietic acid, tetrahydroabietic acid, diabietic acid, neoabietic acid, pimaric acid-type resin acids such as levorotatory pimaric acid, hydrogenated rosins obtained by hydrogenating these, and disproportionated rosins obtained by disproportionating these.

[0145] Examples of commercially available products of the rosin-based resins include PINECRYSTAL D-6011, PINECRYSTAL KE-615-3, PINECRYSTAL KR-614, PINECRYSTAL KE-100, PINECRYSTAL KE-311, PINECRYSTAL KE-359, PINECRYSTAL KE-604, and PINECRYSTAL D-6250 (all manufactured by Arakawa Chemical Industries, Ltd.).

[0146] Examples of the terpene resin include terpene phenol resins and the like.

[0147] The above-mentioned terpene-phenol resin refers to a copolymer of a terpene resin which is an essential oil component obtained from natural products such as rosin and orange peel and phenol, and also includes a partially hydrogenated terpene-phenol resin obtained by hydrogenating at least a portion of the copolymer or a fully hydrogenated terpene-phenol resin obtained by fully hydrogenating the copolymer.

[0148] Here, the fully hydrogenated terpene-phenol resin is a terpene-phenol resin obtained by substantially fully hydrogenating the terpene-phenol resin, and the partially hydrogenated terpene-phenol resin is a terpene-phenol resin obtained by partially hydrogenating the terpene-phenol resin. In addition, the terpene-phenol resin has double bonds derived from terpenes and aromatic ring double bonds derived from phenols. Therefore, the fully hydrogenated terpene-phenol resin refers to a resin in which both the terpene part and the phenol part are completely or almost hydrogenated, and the partially hydrogenated terpene-phenol resin refers to a resin in which the degree of hydrogenation of these parts is not complete but partially hydrogenated. There is no particular limitation on the method and reaction form for the above-mentioned hydrogenation.

[0149] Examples of commercially available products of the terpene-phenol resins include YS Polyster NH (completely hydrogenated terpene-phenol resin) manufactured by Yasuhara Chemical Co., Ltd., and the like.

[0150] The preferred lower limit of the content of the above-mentioned tackifier is 5 parts by mass, and the preferred upper limit is 50 parts by mass, relative to a total of 100 parts by mass of the ultraviolet curable adhesive composition not containing the above-mentioned tackifier. By making the content of the above-mentioned tackifier within this range, the adhesion of the obtained ultraviolet curable adhesive composition to various substrates becomes more excellent. The more preferred lower limit of the content of the above-mentioned tackifier is 10 parts by mass, and the more preferred upper limit is 35 parts by mass.

[0151] The ultraviolet curable adhesive composition of the present invention may contain a plasticizer.

[0152] Examples of the plasticizer include organic acid esters, organic phosphates, and organic phosphites.

[0153] Examples of the organic acid ester include monobasic organic acid esters and polybasic organic acid esters.

[0154] Examples of the monobasic organic acid ester include glycol esters obtained by reacting a monobasic organic acid such as butyric acid, isobutyric acid, hexanoic acid, 2-ethylbutyric acid, heptanoic acid, n-octanoic acid, 2-ethylhexanoic acid, nonanoic acid (n-nonanoic acid), and decanoic acid with a glycol such as triethylene glycol, tetraethylene glycol, and tripropylene glycol.

[0155] Examples of the polybasic organic acid ester include ester compounds obtained by reacting a polybasic organic acid such as adipic acid, sebacic acid, and azelaic acid with an alcohol having a linear or branched structure and having 4 to 8 carbon atoms.

[0156] Specifically, examples of the organic acid esters include triethylene glycol di-2-ethylbutyrate (3GH), triethylene glycol di-2-ethylhexanoate (3GO), triethylene glycol dioctanoate, triethylene glycol di-n-octanoate, triethylene glycol di-n-heptanoate (3G7), etc. In addition, examples include tetraethylene glycol di-n-heptanoate (4G7), tetraethylene glycol di-2-ethylhexanoate, dibutyl sebacate, dioctyl azelate, dibutyl carbitol adipate, ethylene glycol di-2-ethylbutyrate, 1,3-propylene glycol di-2-ethylbutyrate, etc. In addition, examples include 1,4-butanediol di-2-ethylbutyrate, diethylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylhexanoate, dipropylene glycol di-2-ethylbutyrate, etc. In addition, triethylene glycol di-2-ethyl valerate, tetraethylene glycol di-2-ethyl butyrate (4GH), diethylene glycol dioctanoate, dihexyl adipate (DHA), dioctyl adipate, hexylcyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, etc. In addition, oil-modified sebacic acid (Japanese: oil-modified sebacic acid alkyd), a mixture of phosphate and adipate, a mixed adipate made from an alkyl alcohol having 4 to 9 carbon atoms and a cyclic alcohol having 4 to 9 carbon atoms, etc. can be mentioned.

[0157] Examples of the organic phosphate or organic phosphite include compounds obtained by a condensation reaction of phosphoric acid or phosphorous acid with an alcohol, and compounds obtained by a condensation reaction of an alcohol having 1 to 12 carbon atoms with phosphoric acid or phosphorous acid are preferred.

[0158] Examples of the alcohol having 1 to 12 carbon atoms include methanol, ethanol, butanol, hexanol, 2-ethylbutanol, heptanol, octanol, 2-ethylhexanol, decanol, dodecanol, butoxyethanol, butoxyethoxyethanol, and benzyl alcohol.

[0159] Examples of the organic phosphate or organic phosphite include trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tri(2-ethylhexyl) phosphate, tri(butoxyethyl) phosphate, tri(2-ethylhexyl) phosphite, isodecylphenyl phosphate, and triisopropyl phosphate.

[0160] The ultraviolet curable adhesive composition of the present invention may contain a defoaming agent.

[0161] Examples of the defoaming agent include silicone-based defoaming agents, acrylic polymer-based defoaming agents, vinyl ether polymer-based defoaming agents, and olefin polymer-based defoaming agents.

[0162] The ultraviolet curable adhesive composition of the present invention may further contain various known additives such as a crosslinking agent, a viscosity modifier, a silane coupling agent, a sensitizer, a thermosetting agent, a curing retarder, an antioxidant, a storage stabilizer, a dispersant, and a filler within a range not hindering the purpose of the present invention.

[0163] Furthermore, from the viewpoint of preventing a decrease in ultraviolet reactivity, the ultraviolet curable adhesive composition of the present invention preferably contains substantially no organic solvent. Specifically, the content of the organic solvent is preferably 1.5% by mass or less based on 100% by mass of the ultraviolet curable adhesive composition.

[0164] As a method for preparing the ultraviolet curable adhesive composition of the present invention 1, for example, there can be mentioned a method of mixing the maleimide derivative, the ultraviolet polymerizable compound, the photopolymerization initiator, the amine compound, and additives added as required using a mixer, etc. In addition, as a method for preparing the ultraviolet curable adhesive composition of the present invention 2, for example, there can be mentioned a method of mixing the maleimide derivative, the ultraviolet polymerizable compound, the photopolymerization initiator, and additives added as required using a mixer, etc. As the above-mentioned mixer, for example, there can be mentioned a homogenizer disperser, a homogenizer mixer, a universal mixer, a planetary mixer, a kneader, a three-roll mill, etc.

[0165] The ultraviolet curable adhesive composition of the present invention 2 is applied on a substrate, and the total irradiation dose is 900 mJ / cm2 in an atmospheric environment without sealing the upper surface of the coating layer. 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2The reaction rate of the cured product with a thickness of 100 μm is 88% or more. In addition, for the ultraviolet curing adhesive composition of the present invention 1, the ultraviolet curing adhesive composition is applied on a substrate, and the total irradiation amount is 900 mJ / cm2 in an atmospheric environment without sealing the upper surface of the coating layer. 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The reaction rate of the cured product with a thickness of 100 μm is preferably 85% or more. By making the reaction rate of the cured product in the ultraviolet curing adhesive composition of the present invention 1 to be 85% or more, it can be said that the ultraviolet reactivity in the presence of oxygen is sufficiently high, and the ultraviolet curing adhesive composition can be printed into a desired shape and then bonded to the adherend. The more preferred lower limit of the reaction rate of the cured product in the ultraviolet curing adhesive composition of the present invention 1 is 88%.

[0166] As the substrate, a PET film (demolding PET film) with a demoulding treatment applied to the surface is suitable. The above condition is that after the ultraviolet curing adhesive composition is applied to the substrate, ultraviolet irradiation is performed in the presence of oxygen without covering the upper surface of the coating layer with a spacer. Therefore, the reaction rate of the above-mentioned solidified material reflects the ultraviolet reactivity in the presence of oxygen. That is, by making the reaction rate of the above-mentioned solidified material high, the adhesion and low exudation of the ultraviolet curing adhesive composition of the present invention in the presence of oxygen become excellent. The preferred lower limit of the reaction rate of the above-mentioned solidified material is 90%, and the more preferred lower limit is 92%.

[0167] The higher the reaction rate of the cured product, the more preferable it is, but the upper limit is substantially 99%.

[0168] The reaction rate of the solidified material can be specifically measured by the following procedure, for example.

[0169] That is, first, the above-mentioned ultraviolet curable adhesive composition was applied to a release PET film as a substrate. Then, an ultraviolet irradiation device was used so that the total irradiation amount became 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The ultraviolet curable adhesive composition was cured by irradiating light of 100 μm to obtain a cured product having a thickness of 100 μm.

[0170] About 0.3 g of the obtained solidified product was placed on an aluminum pan, and a mixed solvent containing THF: acetone: ethanol in a mass ratio of 8:1:1 was gently added so as not to scatter the solidified product sample, and the solidified product was swollen for about 2 hours. Then, the solidified product was dried at 110°C for 30 minutes, at 170°C for 1 hour, and at 190°C for 30 minutes. Then, the mass of the dried aluminum pan and the dried sample was weighed, and the reaction rate of the solidified product was calculated by the following formula.

[0171] Reaction rate [%] = (total mass of the aluminum pan and the sample after drying - mass of the aluminum pan before drying) / (mass of the sample before swelling) × 100

[0172] The ultraviolet curable adhesive composition of the present invention was applied on a substrate so that the total irradiation amount became 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The glass transition temperature of the cured product having a thickness of 100 μm is preferably -60°C to 20°C. By setting the glass transition temperature of the cured product to be within this range, excellent adhesion to various substrates can be achieved. The glass transition temperature is more preferably 10°C or less.

[0173] Specifically, the glass transition temperature of the cured product can be determined by, for example, the following procedure.

[0174] That is, first, the ultraviolet curable adhesive composition was applied to a release PET film as a substrate. Then, the total irradiation amount was 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The ultraviolet curable adhesive composition was cured by irradiating light of 100 μm to obtain a cured product having a thickness of 100 μm.

[0175] The obtained cured product can be measured using a dynamic viscoelasticity measuring device under the following conditions to determine the tan δ peak temperature as the glass transition temperature. As the dynamic viscoelasticity measuring device, for example, MCR-702e (manufactured by Anton Paar) can be used.

[0176] <Conditions>

[0177] Shear method: Using 8 mm parallel plates, measured by TwinDrive

[0178] Measuring temperature: -70~200℃

[0179] Heating rate: 7℃ / min

[0180] Frequency: 1Hz

[0181] During the temperature drop from 50°C to -70°C at a rate of 10°C / min, preliminary compression bonding was performed at 8N, and measurements were performed from a low temperature as described in the following (1) to (6).

[0182] (1) The temperature was raised at a normal force of 20 N and a strain of 0.005%, and the measurement was performed under this condition until the torque value became less than 1500 μN·m.

[0183] (2) After (1), the temperature was raised at a normal force of 8 N and a strain of 0.05%, and measurement was performed under this condition until the torque value became less than 200 μN·m.

[0184] (3) After (2), the temperature is raised at a normal force of 3 N and a strain of 0.5%, and the torque value is measured under this condition until it becomes less than 150 μN·m. If the torque in (3) is 150 μN·m or more at 120° C., the process is transferred to (4).

[0185] (4) After (3), the temperature was raised at a normal force of 1.5 N and a strain of 2%, and the torque value was measured under this condition until it became less than 100 μN·m. If the torque in (4) was 100 μN·m or more at 170°C, the process was transferred to (5).

[0186] (5) After (4), the temperature is raised at a normal force of 1 N and a strain of 5%, and the measurement is continued under this condition until the torque value is less than 80 μN·m. If the torque of (5) is 80 μN·m or more at 190°C and the thickness is less than 30 μm, the process is transferred to (6).

[0187] (6) After (5), the temperature was raised at a normal force of 1 N and a strain of 10%, and the measurement was continued under this condition until the temperature reached 200° C. When the thickness was less than 20 μm before the temperature in (6) reached 200° C., the measurement was terminated.

[0188] The ultraviolet curable adhesive composition of the present invention is suitable for printing. If the adhesive layer is formed by printing on an adherend (substrate) and applying the desired pattern, the cutting operation can be omitted compared to the case where the sheet-shaped adhesive is cut just before being attached to obtain the adhesive of the desired shape. As a result, the generation of waste can be suppressed and the environmental load can be reduced.

[0189] Examples of a method for printing the ultraviolet curable adhesive composition of the present invention include screen printing, inkjet printing, gravure printing, etc. Among them, screen printing is preferably used.

[0190] The preferred lower limit of the viscosity of the ultraviolet curable adhesive composition of the present invention at 25° C. is 5 mPa·s, and the preferred upper limit is 100000 mPa·s. By making the above-mentioned viscosity within this range, the ultraviolet curable adhesive composition of the present invention is more suitable for printing. The more preferred lower limit of the above-mentioned viscosity is 10 mPa·s, and the more preferred upper limit is 75000 mPa·s.

[0191] The viscosity can be measured, for example, using VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer, using an appropriate cone and plate at each viscosity, under the conditions of 25° C. and 10 rpm.

[0192] The ultraviolet curable adhesive composition of the present invention forms an adhesive layer by irradiating ultraviolet rays and curing it. As a method of using it, an adhesive layer can be formed on a substrate (spacer) to make an adhesive sheet that can be transferred to an adherend, or an adhesive layer can be directly formed on the adherend. In the method of directly forming an adhesive layer on the adherend, the number of laminations can be minimized, and bubbles can be prevented from entering the interface during lamination. On the other hand, in the method of forming an adhesive layer on a substrate (spacer), the adhesive layer is arranged on the adherend by transfer, so it has the advantage of less restrictions on construction.

[0193] The method comprises the steps of applying the ultraviolet curable adhesive composition of the present invention on a first adherend and exposing the composition to form an adhesive layer, and attaching a second adherend to the adhesive layer. The method of applying the ultraviolet curable adhesive composition is inkjet printing, screen printing, spraying, spin coating, gravure offset printing or reverse offset printing. A method for producing a laminated body in which the ultraviolet curable adhesive composition is locally applied to the first adherend is also one of the present invention.

[0194] Examples of the material of the first adherend and the second adherend include metals such as stainless steel and aluminum, and resins.

[0195] The thickness of the adhesive layer is preferably 30 μm or more, more preferably 50 μm or more. By making the thickness of the adhesive layer 30 μm or more, sufficient adhesion can be obtained. In addition, from the perspective of thinning of electronic devices, the thickness of the adhesive layer is preferably 1000 μm or less, more preferably 500 μm or less.

[0196] Effects of the Invention

[0197] According to the present invention, it is possible to provide: a UV-curable adhesive composition having excellent printability, a cured product that is not prone to cohesive failure, and excellent impact resistance; and a UV-curable adhesive composition having excellent adhesiveness and low exudation. In addition, according to the present invention, it is possible to provide a method for producing a laminated body using the UV-curable adhesive composition. DETAILED DESCRIPTION

[0198] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0199] (Examples 1-1 to 1-40, Comparative Examples 1-1 to 1-17)

[0200] The respective materials were mixed according to the mixing ratios described in Tables 1 to 6 using a planetary mixer (manufactured by THINKY CORPORATION, “Awatori Rentaro”) to obtain respective adhesive compositions of Examples 1-1 to 1-40 and Comparative Examples 1-1 to 1-17.

[0201] The details of the materials described by abbreviations in the table are as follows.

[0202] (Maleimide derivatives)

[0203] ·CHMI: N-cyclohexylmaleimide (manufactured by Nippon Shokubai Co., Ltd., a structure without hydrogen bonding to heteroatoms)

[0204] ·LMI: N-laurylmaleimide (manufactured by Seiko Chemical Co., Ltd., a structure without hydrogen bonding to heteroatoms)

[0205] ·HPM: 4-Hydroxyphenylmaleimide (manufactured by Seiko Chemical Co., Ltd., a structure in which hydrogen is bonded to a hetero atom)

[0206] (UV-polymerizable compound)

[0207] ·CBA: Ethyl carbitol acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., "VISCOAT #190", containing an ether bond)

[0208] ·MEDOL-10: (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., contains an ether bond)

[0209] VISCOAT #192: Phenoxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., contains phenoxy group)

[0210] VISCOAT #216: 2-Butylcarbamoyloxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., contains an amide bond)

[0211] ·NOAA: n-octyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.)

[0212] ·4-HBA: 4-Hydroxybutyl acrylate (manufactured by Mitsubishi Chemical Co., Ltd.)

[0213] UA-160TM: Polyether-based multifunctional urethane acrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.)

[0214] ·NVC: N-vinyl-ε-caprolactam (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0215] (Photopolymerization Initiator)

[0216] · Esacure TZT: A mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone (manufactured by IGM Resins, a hydrogen abstraction type photopolymerization initiator)

[0217] ·Omnirad 4MBZ: 4-methylbenzophenone (manufactured by IGM Resins, hydrogen abstraction type photopolymerization initiator)

[0218] · Omnipol TP: polymer of ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate (manufactured by IGM Resins, polymer-type photopolymerization initiator)

[0219] · Omnipol 910: Polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butyrylphenyl)piperazine)propionate (manufactured by IGM Resins, polymer-type photopolymerization initiator)

[0220] · Omnipol 2702: Bis(benzophenone-2-carboxylic acid) polyethylene glycol ester (manufactured by IGM Resins, polymer-type photopolymerization initiator)

[0221] · Omnirad 184: 1-Hydroxycyclohexylphenylketone (manufactured by IGM Resins, a cleavage-type photopolymerization initiator)

[0222] ·Omnirad TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (manufactured by IGM Resins, a cleavage-type photopolymerization initiator)

[0223] ·Omnirad 819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resins, cleavage-type photopolymerization initiator)

[0224] (Amine compounds)

[0225] · Esacure A198: (Bis-N,N-(4-dimethylaminobenzoyl)oxyethylene-1-yl)-methylamine, bis(2-morpholinoethyl) ether (manufactured by IGM Resins, a structure without hydrogen bonding to heteroatoms)

[0226] ·U-cat 660M: Bis(2-morpholinoethyl)ether (manufactured by San-Apro, structure without hydrogen bonding to heteroatoms)

[0227] · Eversorb 93: 1-methyl 10-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate (manufactured by Everlight Chemical, a structure without hydrogen bonding to heteroatoms)

[0228] ・ADK STAB LA-72: Bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate (manufactured by ADEKA, a structure without hydrogen bonding to heteroatoms)

[0229] ・ADK STAB LA-52: Tetrakis (1,2,2,6,6-pentamethyl-4-piperidinyl) butane-1,2,3,4-tetracarboxylate (manufactured by ADEKA, a structure without hydrogen bonding to heteroatoms)

[0230] ・ADK STAB LA-77Y: Bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (manufactured by ADEKA, with a structure in which hydrogen is bonded to a heteroatom)

[0231] ・ADK STAB LA-57: Tetrakis (2,2,6,6-tetramethyl-4-piperidinyl) butane-1,2,3,4-tetracarboxylate (manufactured by ADEKA, with a structure in which hydrogen is bonded to a heteroatom)

[0232] (Thickener)

[0233] ·KE-359: Rosin-based resin (made by Arakawa Chemical Industries, Ltd.)

[0234] (Thermoplastic resin)

[0235] LA2140: Acrylic block copolymer (manufactured by Kuraray Co., Ltd.)

[0236] LA4285: Acrylic block copolymer (manufactured by Kuraray Co., Ltd.)

[0237] (Cross-linking agent)

[0238] ·CORONATE L: Toluene diisocyanate (manufactured by Tosoh Corporation)

[0239] (Reaction rate of cured product)

[0240] The obtained pressure-sensitive adhesive composition was applied onto a release PET film (“1-E” manufactured by NIPPA, Inc., thickness 50 μm) by the method described below to obtain a cured product having a thickness of 100 μm.

[0241] For each adhesive composition obtained in Examples 1-1 to 1-35, 1-40 and Comparative Examples 1-1 to 1-12, 0.5 mL of each adhesive composition was dropped onto a release PET film and applied at 5000 rpm for 10 seconds using a spin coater (manufactured by MIKASA, “MSB-150”) to prepare a thin layer. Next, without sealing the upper surface of the coating layer, an intermittent UV LED curing device (manufactured by AITEC, “M UVBA”) was used in an atmospheric environment to give a total irradiation dose of 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 This operation was repeated until the thickness of the cured product reached 100 μm.

[0242] The adhesive compositions obtained in Examples 1-36 to 1-39 and Comparative Examples 1-13 and 1-14 were applied to a release PET film using a screen printer (SSA-PC560E manufactured by SERIA Corporation) to a thickness of 100 μm. Then, without sealing the upper surface of the coating layer, an intermittent UV LED curing device was used in an atmospheric environment to a total irradiation dose of 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The adhesive composition was cured by irradiating light of 100 μm to obtain a cured product having a thickness of 100 μm. As the intermittent UV LED curing device, M UVBA (manufactured by AITEC) was used.

[0243] The adhesive composition obtained in Comparative Example 1-15 was applied on a release-treated PET film using a coater so as to have a thickness of 100 μm after drying, and dried at 80° C. for 1 hour and at 110° C. for 20 minutes to obtain a cured product.

[0244] For each adhesive composition obtained in Comparative Examples 1-16 and 1-17, the adhesive composition was applied onto a release PET film using an applicator, and the upper surface after application was sealed with a release PET film (manufactured by NIPPA, "1-E", thickness 50 μm), thereby performing UV Wet lamination coating (original text: UV Wet Lamination Coating). An intermittent UV LED curing device was used so that the total irradiation amount was 900 mJ / cm 2 The obtained UVWet laminated coating was irradiated with a wavelength of 365 nm and an illumination of 20 mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The adhesive composition was cured by irradiating light of 100 μm to obtain a cured product having a thickness of 100 μm. As the intermittent UV LED curing device, M UVBA (manufactured by AITEC) was used.

[0245] Take about 0.3 g of the obtained solidified product on an aluminum plate, gently add a mixed solvent containing THF: acetone: ethanol in a mass ratio of 8: 1: 1 so that the solidified product sample does not scatter, and swell it for about 2 hours. Then, dry it at 110°C for 30 minutes, dry it at 170°C for 1 hour, and dry it at 190°C for 30 minutes. Weigh the mass of the dried aluminum plate and the dried sample, and calculate the reaction rate of the solidified product by the following formula.

[0246] Reaction rate [%] = (total mass of the aluminum pan and the sample after drying - mass of the aluminum pan before drying) / (mass of the sample before swelling) × 100

[0247] In addition, the reaction rate of the cured product of each adhesive composition obtained in Examples 1-1 to 1-35 and 1-40 and Comparative Examples 1-1 to 1-12 corresponds to the reaction rate of the cured product of the adhesive composition applied by inkjet printing.

[0248] (Glass transition temperature of cured product)

[0249] The cured product obtained in the same manner as in the above “(Reaction rate of cured product)” was subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring apparatus (MCR-702e, manufactured by Anton Paar) under the following conditions, and the tan δ peak temperature at that time was determined as the glass transition temperature.

[0250] <Conditions>

[0251] Shear method: Using 8 mm parallel plates, measured by TwinDrive

[0252] Measuring temperature: -70~200℃

[0253] Heating rate: 7℃ / min

[0254] Frequency: 1Hz

[0255] During the temperature drop from 50°C to -70°C at a rate of 10°C / min, preliminary compression bonding was performed at 8N, and measurements were performed from a low temperature as described in the following (1) to (6).

[0256] (1) The temperature was raised at a normal force of 20 N and a strain of 0.005%, and the measurement was performed under this condition until the torque value became less than 1500 μN·m.

[0257] (2) After (1), the temperature was raised at a normal force of 8 N and a strain of 0.05%, and measurement was performed under this condition until the torque value became less than 200 μN·m.

[0258] (3) After (2), the temperature is raised at a normal force of 3 N and a strain of 0.5%, and the torque value is measured under this condition until it becomes less than 150 μN·m. If the torque in (3) is 150 μN·m or more at 120° C., the process is transferred to (4).

[0259] (4) After (3), the temperature was raised at a normal force of 1.5 N and a strain of 2%, and the torque value was measured under this condition until it became less than 100 μN·m. If the torque in (4) was 100 μN·m or more at 170°C, the process was transferred to (5).

[0260] (5) After (4), the temperature is raised at a normal force of 1 N and a strain of 5%, and the measurement is continued under this condition until the torque value is less than 80 μN·m. If the torque of (5) is 80 μN·m or more at 190°C and the thickness is less than 30 μm, the process is transferred to (6).

[0261] (6) After (5), the temperature was raised at a normal force of 1 N and a strain of 10%, and the measurement was continued under this condition until the temperature reached 200° C. When the thickness was less than 20 μm before the temperature in (6) reached 200° C., the measurement was terminated.

[0262] <Evaluation>

[0263] The following evaluations were performed on each of the adhesive compositions obtained in Examples 1-1 to 1-40 and Comparative Examples 1-1 to 1-17. The results are shown in Tables 1 to 6.

[0264] (Printability)

[0265] 0.5 mL of each adhesive composition obtained in Examples 1-1 to 1-35, 1-40 and Comparative Examples 1-1 to 1-12 was dropped onto an aluminum substrate of 50 mm×50 mm, and the mixture was applied at 5000 rpm for 10 s using a spin coater (manufactured by MIKASA, “MSB-150”) to prepare a thin layer. Next, an intermittent UV LED curing device (manufactured by AITEC, “M UVBA”) was used to cure the mixture at a total irradiation dose of 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 This operation was repeated until the thickness of the cured product reached 100 μm.

[0266] In addition, 1 part by mass of KS-66 (manufactured by Shin-Etsu Chemical Co., Ltd.) as a defoaming material was added to 100 parts by mass of each adhesive composition obtained in Examples 1-36 to 1-39 and Comparative Examples 1-13 and 1-14 to obtain a screen-printable composition. The obtained screen-printable composition was pattern-coated on a release PET film (manufactured by NIPPA, "1-E", thickness 50 μm) using a screen printer (manufactured by SERIA, "SSA-PC560E") and screen-printed. A 70-mesh printing plate with pattern treatment was used as the screen printing plate. Next, an intermittent UV LED curing device (manufactured by AITEC, "MUVBA") was used to make the total irradiation amount 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 of light, thereby obtaining a solidified material.

[0267] Each cured product obtained was visually confirmed, and the printability was evaluated according to the following criteria. It should be noted that for Examples 1-1 to 1-35, 1-40 and Comparative Examples 1-1 to 1-12, spin coating was performed instead of inkjet printing, and the printability of each adhesive composition obtained in Examples 1-1 to 1-35, 1-40 and Comparative Examples 1-1 to 1-12 corresponded to the printability in inkjet printing.

[0268] ○: There is no uncured part and no bleeding (Japanese: にじみ) was observed

[0269] ×: There is an uncured portion, or there is no uncured portion but bleeding is observed

[0270] (Adhesion and peeling mode)

[0271] (1) Preparation of test pieces

[0272] (1-1) Examples 1-1 to 1-35, 1-40 and Comparative Examples 1-1 to 1-12

[0273] For each adhesive composition obtained in Examples 1-1 to 1-35, 1-40 and Comparative Examples 1-1 to 1-12, 0.5 mL of each adhesive composition was dropped onto a release PET film (manufactured by NIPPA, "1-E", thickness 50 μm), and applied at 5000 rpm for 10 seconds using a spin coater to prepare a thin layer with a width of 50 mm and a length of 50 mm. As the spin coater, MSB-150 (manufactured by MIKASA) was used. Then, an intermittent UV LED curing device (manufactured by AITEC, "M UVBA") was used to make the total irradiation amount 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 By repeating this operation, a cured product with a thickness of 100 μm was obtained.

[0274] Next, the cured product was sealed with an easily adhesive polyester film (Cosmoshine A4100 manufactured by Toyobo Co., Ltd.) with a width of 50 mm and a length of 200 mm, and cut to a width of 25 mm and a length of 200 mm (adhesive surface 20 mm × 50 mm) to prepare a laminated film. Then, the release PET film was peeled off from the laminated film, and the exposed surface was bonded to the SUS substrate, and a 2 kg roller was reciprocated once to perform pressure bonding to obtain a test piece.

[0275] (1-2) Examples 1-36 to 1-39 and Comparative Examples 1-13 and 1-14

[0276] The adhesive compositions obtained in Examples 1-36 to 1-39 and Comparative Examples 1-13 and 1-14 were applied to an adhesive polyester film (Cosmoshine A4100, manufactured by Toyobo Co., Ltd.) using a screen printer (SSA-PC560E, manufactured by SERIA) to a thickness of 100 μm. Then, an intermittent UV LED curing device (M UVBA, manufactured by AITEC) was used to cure the film at a total irradiation dose of 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2The adhesive composition was cured by irradiating light of 100 μm to obtain a cured product having a thickness of 100 μm.

[0277] Next, the air surface of the cured product was sealed with a release PET film (manufactured by NIPPA, "1-E", thickness 50 μm), and cut to a width of 25 mm and a length of 200 mm (adhesive surface 25 mm × 80 mm) to produce a laminated film. Then, the release PET film was peeled off from the laminated film, and the exposed surface was bonded to the SUS substrate, and a 2 kg roller was reciprocated once to perform pressure bonding to obtain a test piece.

[0278] (1-3) Comparative Example 1-15

[0279] The adhesive composition obtained in Comparative Example 1-15 was applied onto a highly adhesive polyester film (Cosmoshine A4100 manufactured by Toyobo Co., Ltd.) using a coater so as to have a thickness of 100 μm after drying, and dried at 80° C. for 1 hour and at 110° C. for 20 minutes to obtain a cured product.

[0280] Next, the air surface of the cured product was sealed with a release PET film (manufactured by NIPPA, "1-E", thickness 50 μm), and cut to a width of 25 mm and a length of 200 mm (adhesive surface 25 mm × 80 mm) to produce a laminated film. Then, the release PET film was peeled off from the laminated film, and the exposed surface was bonded to the SUS substrate, and a 2 kg roller was reciprocated once to perform pressure bonding to obtain a test piece.

[0281] (1-4) Comparative Examples 1-16 and 1-17

[0282] For each adhesive composition obtained in Comparative Examples 1-16 and 1-17, the adhesive composition was applied onto an easily adhesive polyester film (manufactured by Toyobo Co., Ltd., "Cosmoshine A4100") using an applicator, and the upper surface after application was sealed with a release PET film (manufactured by NIPPA Co., Ltd., "1-E", thickness 50 μm), thereby performing UVWet lamination coating. An intermittent UV LED curing device was used so that the total irradiation amount was 900 mJ / cm 2 The obtained UVWet laminated coating was irradiated with a wavelength of 365 nm and an illumination of 20 mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The adhesive composition was cured by irradiating light of 100 μm to obtain a cured product having a thickness of 100 μm. As the intermittent UV LED curing device, M UVBA (manufactured by AITEC) was used.

[0283] Next, the laminate film was cut into 25 mm in width and 200 mm in length (bonded surface 25 mm×80 mm) to prepare a laminate film. The release PET film was then peeled off from the laminate film, and the exposed surface was bonded to the SUS substrate and pressed with a 2 kg roller reciprocated once to obtain a test piece.

[0284] (2) Measurement of adhesive strength and confirmation of peeling mode

[0285] The obtained test piece was cured for 1 day in an environment of 25° C. and 50% RH, and then the adhesive strength was measured by performing 180° peeling at a speed of 300 mm / min using a universal testing machine (TENSILON RTI-1310 manufactured by A&D Corporation).

[0286] In addition, the peeling mode at the time of 180° peeling was evaluated according to the following criteria.

[0287] AF: Interface peeling

[0288] WLB: cohesive peeling near the interface

[0289] Zip: Zipper peeling

[0290] CF: Cohesive failure

[0291] It should be noted that AF and WLB are preferred results, Zip is a worse result than them, and CF is an even worse result.

[0292] (Impact resistance)

[0293] The impact resistance test was performed on the cured product obtained in the same manner as in the above-mentioned "(Reaction rate of cured product)" by the following method.

[0294] A 40mm×40mm×3mmt SUS substrate with a 20mm×20mm×3mmt hole in the center was bonded to a 25mm×25mm×3mmt SUS substrate through a cured product cut into 25mm×25mm to obtain a laminate. The obtained laminate was crimped at 62N using a universal testing machine (manufactured by A&D, "TENSILON RTI-1310") to produce a test piece. A drop hammer impact tester (manufactured by IMATEK, "IM1C-15") was used to impact the center of the test piece from a height of 51mm by natural drop with a 16Φ drop hammer with a total mass of 5kg. Based on the spectrum of ms vs N, the area of ​​the first peak (amount of energy) was used as the impact absorption rate ΔE[J], and the peak force (impact test force[N]) was calculated. The impact resistance was evaluated according to the following criteria.

[0295] ◎: When ΔE exceeds 0.3J or the peak force exceeds 1.4N

[0296] ○: When ΔE is 0.15 J or more and 0.3 J or less and the peak force is 0.8 N or more and 1.4 N or less

[0297] ×: When ΔE is less than 0.15 J and the peak force is 0.8 N to 1.4 N

[0298] ××: When ΔE is less than 0.15J and the peak force is less than 0.8N

[0299] [Table 1]

[0300]

[0301] [Table 2]

[0302]

[0303] [Table 3]

[0304]

[0305] [Table 4]

[0306]

[0307] [Table 5]

[0308]

[0309] [Table 6]

[0310]

[0311] (Examples 2-1 to 2-20, Comparative Examples 2-1 to 2-3)

[0312] The materials were mixed according to the mixing ratios described in Tables 7 to 9 using a planetary mixer (manufactured by THINKY CORPORATION, “Awatori Rentaro”) to obtain adhesive compositions of Examples 2-1 to 2-20 and Comparative Examples 2-1 to 2-3.

[0313] The details of the materials described by abbreviations in the table are as follows.

[0314] (Maleimide derivatives)

[0315] ·CHMI: N-cyclohexylmaleimide (manufactured by Nippon Shokubai Co., Ltd.)

[0316] ·HPM: 4-Hydroxyphenylmaleimide (manufactured by Seiko Chemical Co., Ltd.)

[0317] ·NCCHMI: N-(4-carboxycyclohexylmethyl)maleimide (manufactured by Seiko Chemical Co., Ltd.)

[0318] (UV-polymerizable compound)

[0319] ·CBA: Ethyl carbitol acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., "VISCOAT #190", containing an ether bond)

[0320] ·MEDOL-10: (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., contains an ether bond)

[0321] VISCOAT #192: Phenoxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., contains phenoxy group)

[0322] VISCOAT #216: 2-Butylcarbamoyloxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., contains an amide bond)

[0323] ·NOAA: n-octyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.)

[0324] ·4-HBA: 4-Hydroxybutyl acrylate (manufactured by Mitsubishi Chemical Co., Ltd.)

[0325] UA-160TM: Polyether-based multifunctional urethane acrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.)

[0326] ·NVC: N-vinyl-ε-caprolactam (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0327] (Photopolymerization Initiator)

[0328] · Omnirad 184: 1-Hydroxycyclohexylphenylketone (manufactured by IGM Resins, a cleavage-type photopolymerization initiator)

[0329] ·Omnirad TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (manufactured by IGM Resins, a cleavage-type photopolymerization initiator)

[0330] ·Omnirad 819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resins, cleavage-type photopolymerization initiator)

[0331] · Esacure 1001M: 1-(4-(4-benzoylphenylthio)phenyl)-2-toluenesulfonyl-2-methyl-1-propanone (manufactured by IGM Resins, hydrogen abstraction type photopolymerization initiator)

[0332] ·Esacure 3644: 3-Ketocoumarin (manufactured by IGM Resins, hydrogen abstraction type photopolymerization initiator)

[0333] (Amine compounds)

[0334] · Esacure A198: (Bis-N,N-(4-dimethylaminobenzoyl)oxyethylene-1-yl)-methylamine, bis(2-morpholinoethyl) ether (manufactured by IGM Resins Co., Ltd.)

[0335] ·U-cat 660M: Bis(2-morpholinoethyl)ether (manufactured by San-Apro)

[0336] (Thickener)

[0337] ·KE-359: Rosin-based resin (made by Arakawa Chemical Industries, Ltd.)

[0338] (Thermoplastic resin)

[0339] LA2140: Acrylic block copolymer (manufactured by Kuraray Co., Ltd.)

[0340] The acrylic polymers as thermoplastic resins used in Examples 2-1 to 2-20 and Comparative Examples 2-1 to 2-3 were prepared by the following method.

[0341] In a 2L separable flask equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube, 100 parts by mass of 2-ethylhexyl acrylate, 3 parts by mass of acrylic acid, 0.1 parts by mass of 2-hydroxyethyl acrylate, and 300 parts by mass of ethyl acetate as a polymerization solvent were added. Next, nitrogen gas was blown in for 30 minutes to replace the inside of the reaction container with nitrogen, and the reaction container was heated to 80°C while stirring. After 30 minutes, 0.5 parts by mass of tert-butyl peroxy-2-ethylhexanoate (1-hour half-life temperature: 92.1°C, 10-hour half-life temperature: 72.1°C) as a polymerization initiator was diluted with 5 parts by mass of ethyl acetate, and the obtained polymerization initiator solution was added dropwise to the reaction container over 6 hours. Then, after further reacting at 80°C for 6 hours, the reaction solution was cooled, thereby obtaining an acrylic polymer solution.

[0342] The obtained acrylic polymer solution was diluted with a diluting solvent (a mixed solvent of methanol and toluene, with a mass ratio of methanol to toluene of 1:2) to prepare a solution with a solid content of 20% by mass. Next, the solution was applied on a release-treated PET film using a coater so that the thickness after drying was 100 μm, and dried at 80° C. for 1 hour and at 110° C. for 20 minutes to obtain an acrylic polymer.

[0343] (Viscosity)

[0344] 0.4 mL of the obtained PSA composition was collected and the viscosity was measured at 25° C. and 10 rpm using VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer using an appropriate cone and plate at each viscosity.

[0345] (Reaction rate of cured product)

[0346] The obtained pressure-sensitive adhesive composition was applied onto a release PET film (“1-E” manufactured by NIPPA, Inc., thickness 50 μm) by the method described below to obtain a cured product having a thickness of 100 μm.

[0347] The adhesive compositions obtained in Examples 2-1 to 2-14, 2-16 to 2-20 and Comparative Examples 2-1 to 2-3 were applied to a release PET film using a screen printer (SSA-PC560E manufactured by SERIA Corporation) to a thickness of 100 μm. Then, without sealing the upper surface of the coating layer, an intermittent UV LED curing device was used in an atmospheric environment to a total irradiation dose of 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The adhesive composition was cured by irradiating light of 100 μm to obtain a cured product having a thickness of 100 μm. As the intermittent UV LED curing device, M UVBA (manufactured by AITEC) was used.

[0348] 0.5 mL of the adhesive composition obtained in Example 2-15 was dropped onto a release PET film and coated at 5000 rpm for 10 seconds using a spin coater (manufactured by MIKASA, “MSB-150”) to prepare a thin layer. Next, without sealing the upper surface of the coating layer, an intermittent UV LED curing device (manufactured by AITEC, “M UVBA”) was used in an atmospheric environment to cure the film with a total irradiation dose of 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 This operation was repeated until the thickness of the cured product reached 100 μm.

[0349] Take about 0.3 g of the obtained solidified product on an aluminum plate, gently add a mixed solvent containing THF: acetone: ethanol in a mass ratio of 8:1:1 so that the solidified product sample does not scatter, and swell it for about 2 hours. Then, dry it at 110°C for 30 minutes, dry it at 170°C for 1 hour, and dry it at 190°C for 30 minutes. Weigh the mass of the dried aluminum plate and the dried sample, and calculate the reaction rate of the solidified product by the following formula.

[0350] Reaction rate [%] = (total mass of the aluminum pan and the sample after drying - mass of the aluminum pan before drying) / (mass of the sample before swelling) × 100

[0351] It should be noted that, in Example 2-15, spin coating was performed instead of inkjet printing, and the reaction rate of the cured product of the adhesive composition obtained in Example 2-15 corresponds to the reaction rate of the cured product of the adhesive composition applied by inkjet printing.

[0352] (Glass transition temperature of cured product)

[0353] The cured product obtained in the same manner as in the above “(Reaction rate of cured product)” was subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring apparatus (MCR-702e, manufactured by Anton Paar) under the following conditions, and the tan δ peak temperature at that time was determined as the glass transition temperature.

[0354] <Conditions>

[0355] Shear method: Using 8 mm parallel plates, measured by TwinDrive

[0356] Measuring temperature: -70~200℃

[0357] Heating rate: 7℃ / min

[0358] Frequency: 1Hz

[0359] During the temperature drop from 50°C to -70°C at a rate of 10°C / min, preliminary compression bonding was performed at 8N, and measurements were performed from a low temperature as described in the following (1) to (6).

[0360] (1) The temperature was raised at a normal force of 20 N and a strain of 0.005%, and the measurement was performed under this condition until the torque value became less than 1500 μN·m.

[0361] (2) After (1), the temperature was raised at a normal force of 8 N and a strain of 0.05%, and measurement was performed under this condition until the torque value became less than 200 μN·m.

[0362] (3) After (2), the temperature is raised at a normal force of 3 N and a strain of 0.5%, and the torque value is measured under this condition until it becomes less than 150 μN·m. If the torque value of (3) is 150 μN·m or more at 120°C, the process is transferred to (4).

[0363] (4) After (3), the temperature was raised at a normal force of 1.5 N and a strain of 2%, and the torque value was measured under this condition until it became less than 100 μN·m. If the torque value of (4) was 100 μN·m or more at 170°C, the process was transferred to (5).

[0364] (5) After (4), the temperature is raised at a normal force of 1 N and a strain of 5%, and the measurement is continued under this condition until the torque value is less than 80 μN·m. If the torque value of (5) is 80 μN·m or more at 190°C and the thickness is less than 30 μm, the process is transferred to (6).

[0365] (6) After (5), the temperature was raised at a normal force of 1 N and a strain of 10%, and the measurement was continued under this condition until the temperature reached 200° C. When the thickness was less than 20 μm before the temperature in (6) reached 200° C., the measurement was terminated.

[0366] <Evaluation>

[0367] The following evaluations were performed on each of the adhesive compositions obtained in Examples 2-1 to 2-20 and Comparative Examples 2-1 to 2-3. The results are shown in Tables 7 to 9.

[0368] (Adhesion (Open) and Peel Mode)

[0369] (1) Preparation of test pieces

[0370] (1-1) Examples 2-1 to 2-14, 2-16 to 2-20 and Comparative Examples 2-1 to 2-3

[0371] For each adhesive composition obtained in Examples 2-1 to 2-14, 2-16 to 2-20 and Comparative Examples 2-1 to 2-3, the adhesive composition was applied to an easily adhesive polyester film (manufactured by Toyobo Co., Ltd., "Cosmoshine A4100") using a screen printer so as to have a thickness of 100 μm, a width of 25 mm, and a length of 80 mm. As the screen printer, SSA-PC560E (manufactured by SERIA) was used. Then, without sealing the upper surface of the coating layer, an intermittent UV LED curing device was used in an atmospheric environment so that the total irradiation amount was 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm2 The adhesive composition was cured by irradiating light of 100 μm to obtain a cured product having a thickness of 100 μm. As the intermittent UV LED curing device, M UVBA (manufactured by AITEC) was used.

[0372] Next, the air surface of the cured product was sealed with a release PET film (manufactured by NIPPA, "1-E", thickness 50 μm), and cut to a width of 25 mm and a length of 200 mm to produce a laminated film. Then, the release PET film was peeled off from the laminated film, and the exposed surface was bonded to the SUS substrate, and a 2 kg roller was reciprocated once to perform pressure bonding to obtain a test piece.

[0373] (1-2) Example 2-15

[0374] For each adhesive composition obtained in Examples 2 to 15, 0.5 mL of each adhesive composition was dropped onto a release PET film (manufactured by NIPPA, "1-E", thickness 50 μm), and applied at 5000 rpm for 10 seconds using a spin coater (manufactured by MIKASA, "MSB-150") to prepare a thin layer with a width of 50 mm and a length of 50 mm. Then, an intermittent UV LED curing device (manufactured by AITEC, "M UVBA") was used to make a total irradiation dose of 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 By repeating this operation, a cured product with a thickness of 100 μm was obtained.

[0375] Next, the cured product was sealed with an easily adhesive polyester film (Cosmoshine A4100 manufactured by Toyobo Co., Ltd.) with a width of 50 mm and a length of 200 mm, and cut to a width of 25 mm and a length of 200 mm (adhesive surface 20 mm × 50 mm) to prepare a laminated film. Then, the release PET film was peeled off from the laminated film, and the exposed surface was bonded to the SUS substrate, and a 2 kg roller was reciprocated once to perform pressure bonding to obtain a test piece.

[0376] (2) Measurement of adhesive strength and confirmation of peeling mode

[0377] The obtained test piece was cured for 1 day in an environment of 25° C. and 50% RH, and then the adhesive strength (Open) was measured by performing 180° peeling at a speed of 300 mm / min using a universal testing machine (TENSILON RTI-1310 manufactured by A&D Corporation).

[0378] In addition, the peeling mode at the time of 180° peeling was evaluated according to the following criteria.

[0379] AF: Interface peeling

[0380] WLB: cohesive peeling near the interface

[0381] Zip: Zipper stripping

[0382] CF: Cohesive failure

[0383] It should be noted that AF and WLB are preferred results, Zip is a worse result than them, and CF is an even worse result.

[0384] (Adhesion (Close) and Adhesion Ratio)

[0385] As a reference for comparison of the above-mentioned adhesive force (Open), the adhesive force (Close) was measured.

[0386] For the composition in which the components other than the photopolymerization initiator were the same as those of Examples 2-1 to 2-20 and Comparative Examples 2-1 to 2-3, 0.5 parts by mass of Omnirad 184, Omnirad TPO, and Omnirad 819 were added to 100 parts by mass of the total of the maleimide derivative and the ultraviolet polymerizable compound, and mixed using a planetary mixer to obtain an adhesive composition. As the planetary mixer, Awatori Rentaro (manufactured by THINKY Co., Ltd.) was used.

[0387] Each of the obtained adhesive compositions was applied to an adhesive polyester film (Toyobo Co., Ltd., Cosmoshine A4100) using a screen printer (SERIA Co., Ltd., SSA-PC560E) to a thickness of 100 μm. The upper surface (atmospheric surface) of the coating layer was then sealed with a release PET film (NIPPA Co., Ltd., 1-E, 50 μm thick). An intermittent UV LED curing device was then used to cure the film with a total irradiation dose of 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The adhesive composition was cured by irradiating light of 100 μm to obtain a cured product having a thickness of 100 μm. As the intermittent UV LED curing device, M UVBA (manufactured by AITEC) was used.

[0388] Next, the obtained laminate of the highly adhesive polyester film, the cured product, and the release PET film was cut into a width of 25 mm and a length of 200 mm (adhesive surface 25 mm×80 mm) to prepare a laminated film. Then, the release PET film was peeled off from the laminated film, and the exposed surface was bonded to the SUS substrate, and a 2 kg roller was reciprocated once to perform pressure bonding to obtain a test piece.

[0389] The obtained test piece was cured for 1 day in an environment of 25°C and 50% RH, and then peeled 180° at a speed of 300 mm / min using a universal testing machine (TENSILON RTI-1310 manufactured by A&D Co., Ltd.) to measure the adhesive strength (Close). In addition, (adhesive strength (Open) / adhesive strength (Close))×100 was calculated as the adhesive strength ratio.

[0390] (Low exudability)

[0391] For the cured product obtained in the same manner as in the above "(Reaction rate of cured product)", five lines of about 1 cm in length were drawn on the surface at intervals of about 2 mm using an oil-based marker ("Mckee" manufactured by ZEBRA), and the state of each line was visually observed. Low exudation properties were evaluated according to the following criteria.

[0392] ○: All five lines are drawn without any white space.

[0393] △: All five lines are drawn, but one or more lines have white spots.

[0394] ×: Cannot draw more than one line

[0395] [Table 7]

[0396]

[0397] [Table 8]

[0398]

[0399] [Table 9]

[0400]

[0401] Industrial Applicability

[0402] According to the present invention, it is possible to provide: a UV-curable adhesive composition having excellent printability, a cured product that is not prone to cohesive failure, and excellent impact resistance; and a UV-curable adhesive composition having excellent adhesiveness and low exudation. In addition, according to the present invention, it is possible to provide a method for producing a laminated body using the UV-curable adhesive composition.

Claims

1. A UV-curable adhesive composition, characterized in that: Contains a maleimide derivative, an ultraviolet polymerizable compound, a photopolymerization initiator and an amine compound, In the case where the maleimide derivative includes a maleimide derivative having no structure of hydrogen bonding to a heteroatom, the maleimide derivative does not include a maleimide derivative having a structure of hydrogen bonding to a heteroatom, or the content of the maleimide derivative having a structure of hydrogen bonding to a heteroatom in the maleimide derivative is less than 50% by mass, When the maleimide derivative contains only a maleimide derivative having a structure in which a hydrogen atom is bonded to a heteroatom, the content of the maleimide derivative having a structure in which a hydrogen atom is bonded to a heteroatom is 9.8 parts by mass or less relative to 100 parts by mass of the ultraviolet polymerizable compound, The ultraviolet polymerizable compound contains 20% by mass or more of a monomer capable of serving as a hydrogen donor, The photopolymerization initiator comprises at least one selected from a hydrogen abstraction type photopolymerization initiator and a polymer type photopolymerization initiator, The amine compound has a content of 50% by mass or more of an amine compound having no structure in which hydrogen bonds to a hetero atom. The content of the amine compound is 0.1 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the total of the maleimide derivative and the ultraviolet polymerizable compound.

2. The ultraviolet curable adhesive composition according to claim 1, wherein The content of the maleimide derivative is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the ultraviolet polymerizable compound.

3. The ultraviolet curable adhesive composition according to claim 1 or 2, wherein The monomer capable of serving as a hydrogen donor is a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond.

4. The ultraviolet curable adhesive composition according to claim 1, 2 or 3, wherein The ultraviolet curable adhesive composition was applied on a substrate, and the total irradiation dose was 900 mJ / cm2 in an atmospheric environment without sealing the upper surface of the coating layer. 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The reaction rate of the cured product with a thickness of 100 μm was 85% or more.

5. A UV-curable adhesive composition, characterized in that: Contains maleimide derivatives, ultraviolet polymerizable compounds and photopolymerization initiators. The content of the maleimide derivative is 8 parts by mass or more relative to 100 parts by mass of the ultraviolet polymerizable compound. The ultraviolet curable adhesive composition was applied on a substrate, and the total irradiation dose was 900 mJ / cm2 in an atmospheric environment without sealing the upper surface of the coating layer. 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The reaction rate of the cured product with a thickness of 100 μm was 88% or more. The ultraviolet curable adhesive composition according to claim 5 , further comprising an amine compound.

7. The ultraviolet curable adhesive composition according to claim 1, 2, 3, 4, 5 or 6, wherein The ultraviolet polymerizable compound contains 50% by mass or more of a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond.

8. The ultraviolet curable adhesive composition according to claim 1, 2, 3, 4, 5, 6 or 7, wherein The ultraviolet polymerizable compound includes at least one selected from the group consisting of a (meth)acrylic monomer and a vinyl monomer.

9. The ultraviolet curable adhesive composition according to claim 8, wherein The ultraviolet polymerizable compound includes a multifunctional (meth)acrylic monomer.

10. The ultraviolet curable adhesive composition according to claim 9, wherein The ultraviolet polymerizable compound comprises a multifunctional (meth)acrylic monomer, The content of the polyfunctional (meth)acrylic monomer is 25 parts by mass or less based on 100 parts by mass of the total of the maleimide derivative and the ultraviolet polymerizable compound excluding the polyfunctional (meth)acrylic monomer.

11. The ultraviolet curable adhesive composition according to claim 10, wherein The content of the polyfunctional (meth)acrylic monomer is 20 parts by mass or less based on 100 parts by mass of the total of the maleimide derivative and the ultraviolet polymerizable compound excluding the polyfunctional (meth)acrylic monomer.

12. The ultraviolet curable adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or 11, wherein The content of the photopolymerization initiator is 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the total of the maleimide derivative and the ultraviolet polymerizable compound.

13. The ultraviolet curable adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, further comprising a thermoplastic resin.

14. The ultraviolet curable adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, further comprising a tackifier.

15. The ultraviolet curable adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, which has a viscosity of 10 mPa·s or more and 75000 mPa·s or less at 25°C.

16. The ultraviolet curable adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, wherein The ultraviolet curable adhesive composition was applied on the substrate so that the total irradiation amount became 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The glass transition temperature of the cured product having a thickness of 100 μm obtained by irradiating the cured product with light is -60°C or higher and 20°C or lower.

17. A method for producing a laminate, comprising: a step of applying the ultraviolet curable adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16 on a first adherend and exposing the composition to form an adhesive layer; and a step of attaching a second adherend to the adhesive layer. The method of applying the ultraviolet curable adhesive composition is inkjet printing, screen printing, spray coating, spin coating, gravure offset printing or reverse offset printing, and the ultraviolet curable adhesive composition is locally applied on the first adherend.

Citation Information

Patent Citations

  • Radiation-curing adhesive composition and laminate using the same

    JP2013216742A

  • Photocurable adhesive composition

    WO2016163152A1